Sealing sheet and display

By using a sealing sheet with a resin composition layer with a refractive index of 1.45 to 1.65 and a protective film in the optical semiconductor element, the problems of buriedness and seamlessness of micro-size optical semiconductor elements are solved, and the brightness of micro-LED displays are improved and Visual effects.

CN119318228APending Publication Date: 2025-01-14아티엔스가부시키가이샤 +1

Patent Information

Application Number
CN202480002748.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-08-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing optical semiconductor element sealing sheets are difficult to follow micro-size optical semiconductor elements, resulting in the existence of voids, affecting brightness and seamlessness. The conspicuous module seam problem in micro LED displays has not been effectively solved.

Method used

A sealing sheet containing a protective film and a resin composition layer is adopted, which contains metal oxide particles of 5 nm to 50 nm and a specific resin with a refractive index of 1.45 to 1.65. The loss tangent peak intensity and color are optimized by dynamic viscoelastic determination. Space color ensures buriedness, seamlessness and adhesion.

Benefits of technology

It realizes excellent buriedness and seamlessness of micro LED components, improves the visual recognition and adhesion of the display, and simplifies the manufacturing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318228A_ABST
    Figure CN119318228A_ABST
Patent Text Reader

Abstract

The invention provides a sealing sheet and a display, which are excellent in embedding property and seamless property when an optical semiconductor element is sealed, and are also excellent in embedding property and seamless property even when the sealing sheet is applied to a display in which a micro LED is used as a light source. A sealing sheet (1) for sealing an optical semiconductor element (5), in which a protective film and a resin composition layer (2) are arranged in this order, the resin composition layer (2) contains 5.3-48.2 parts by mass of metal oxide particles (B) per 100 parts by mass of the total of a resin (A), a monomer, and an oligomer, and the number average primary particle diameter of the metal oxide particles (B) is 5-50 nm. The refractive index of the resin composition layer (2) is 1.45 to 1.65.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a sealing sheet, and more particularly to a sealing sheet including a resin composition layer for sealing optical semiconductor elements used in various products such as electronic devices and displays, and a display equipped with the resin composition layer. Background Art

[0002] In recent years, with regard to displays, the development of various light-emitting elements is being actively carried out with the goal of further high performance. Specifically, various display specifications such as backlight displays using liquid crystals or quantum dots, displays using self-luminous elements such as mini / micro light emitting diodes (LED) or organic electroluminescence (EL), plasma displays, and electrophoretic displays have been studied, and a wide range of applications ranging from large display uses such as signage or televisions to small-sized uses such as tablets, personal computers, smartphones, and wearable devices have been studied. In particular, the development of displays using LEDs is progressing day by day, and Patent Document 1 describes a thermosetting resin composition for sealing LED elements. In addition, Patent Document 2 discloses a transparent thermally conductive composition containing a resin and a filler that can be used as a sealing material for an optical semiconductor. The filler includes a thermal conductive filler with an average particle size of 1 μm to 100 μm and a thermal conductivity of 2 W / m·K or more, and a high refractive index filler with an average particle size of 1 nm to 100 nm and a refractive index of 1.8 or more as essential components. As the next generation display technology, the most popular is the micro LED display.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2021 / 200035 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Patent document 1 describes a sheet for sealing optical semiconductor elements that is easy to operate, can be used in a simple process, and can seal optical semiconductor elements in a short time. However, in recent years, in optical semiconductor elements that have been miniaturized, the intervals between optical semiconductor elements have become narrower, and the sheet-like resin composition described in Patent document 1 is difficult to follow the micro-sized optical semiconductor elements to fill the gaps (embeddability). In the case where there is a gap between the optical semiconductor element and the sealing resin composition, especially in an LED display module, the brightness will be reduced due to the refraction of light in the gap.

[0008] In addition, micro-LED displays are formed by connecting small micro-LED display modules of about 9 inches to 10 inches vertically and horizontally into blocks to form a large screen. In this case, when the display is viewed at a close distance, the problem of the joints of the modules being noticeable (seamless) arises. In addition to high brightness, in order to make a display with inconspicuous joints, a sealing sheet with excellent embedding properties and seamlessness is required.

[0009] The present disclosure is made in view of the above-mentioned problems, and its subject is to provide a sealing sheet with excellent embedding property of optical semiconductor elements. In addition, its subject is to provide a sealing sheet and a display having a resin composition layer, which have excellent embedding property and seamlessness as well as excellent visibility, especially when applied to a display using a micro LED element as a light source. In addition, as a further subject, from the perspective of simplifying the manufacturing process of the micro LED display, a sealing sheet with excellent adhesion to the substrate is provided.

[0010] Technical means of solving problems

[0011] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by the sealing sheet described below, thereby completing the present inventions [1] to [9] described below.

[0012] [1] A sealing sheet for sealing an optical semiconductor element, the sealing sheet comprising a protective film and a resin composition layer in this order, the resin composition layer containing a resin (A) and metal oxide particles (B), the number average primary particle size of the metal oxide particles (B) being 5 nm to 50 nm, and the refractive index of the resin composition layer being 1.45 to 1.65.

[0013] [2]: The sealing sheet according to [1], wherein the metal constituting the metal oxide particles (B) includes at least one selected from the group consisting of Ti, Al, and Zr.

[0014] [3]: The sealing sheet according to [1] or [2], wherein the resin (A) comprises at least one selected from the group consisting of (meth)acrylic resins (a) and urethane resins (b).

[0015] [4]: The sealing sheet according to any one of [1] to [3], wherein the resin composition layer has a haze of 12% or less, a total light transmittance of 80% or more, and the resin composition layer has a CIE (International Commission on Illumination) L * a * b * The chroma C obtained from the color space * It ranges from 0 to 10.

[0016] [5]: The sealing sheet according to any one of [1] to [4], wherein the thickness Ta of the resin composition layer is 1 μm to 100 μm, and the thickness Tb of the protective film is 10 μm to 188 μm.

[0017] [6]: The sealing sheet according to any one of [1] to [5], wherein the protective film is directly laminated on the resin composition layer, and the ratio of the root mean square height Sq specified by the International Organization for Standardization (ISO) 25178 in the surface of the protective film in contact with the resin composition layer to the thickness Ta of the resin composition layer is 0.01% to 30%.

[0018] [7]: The sealing sheet according to any one of [1] to [6], wherein the peak top strength (tan δ peak strength) of the loss tangent of the resin composition layer obtained by dynamic viscoelasticity measurement in the range of -50°C to 80°C is 0.6 to 2.2.

[0019] [8]: The sealing sheet according to any one of [1] to [7], wherein the optical semiconductor element is a micro LED.

[0020] [9]: The sealing sheet according to any one of [1] to [8], wherein the resin composition layer contains 5.3 to 48.2 parts by mass of the metal oxide (B) based on 100 parts by mass of the total of the resin (A), the monomer, and the oligomer.

[0021]

[10] : A display having a sealing layer, wherein the sealing layer contains a resin (A) and metal oxide particles (B), wherein the number average primary particle size of the metal oxide particles (B) is 5 nm to 50 nm, and the refractive index of the sealing layer is 1.45 to 1.65.

[0022]

[11] : The display according to

[10] , comprising 5.3 to 48.2 parts by mass of the metal oxide particles (B) based on 100 parts by mass of the total of the resin (A), the monomer, and the oligomer.

[0023] Effects of the Invention

[0024] The present disclosure can provide a sealing sheet and a display having a resin composition layer that are excellent in embedding properties of optical semiconductor elements, particularly when applied to a display using a micro LED element as a light source, and are also excellent in embedding properties, seamlessness, adhesion, and visibility. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] [ Figure 1A ] is a schematic cross-sectional view showing an example of a stacked structure of a sealing sheet.

[0026] [ Figure 1B ] is a schematic cross-sectional view showing another example of a stacked structure of a sealing sheet.

[0027] [ Figure 2 ] is a schematic cross-sectional view showing the process of forming a sealing layer on a substrate having an optical semiconductor element.

[0028] [ Figure 3 ] is a cross-sectional view showing an example of a test substrate that imitates a micro-LED substrate. DETAILED DESCRIPTION

[0029] Hereinafter, the present disclosure will be described in detail. In addition, the embodiment described below is an example of the present disclosure. The present disclosure is not limited to the following embodiment, and also includes modifications implemented within the scope of the main purpose of the present disclosure. In this specification, the numerical range specified by "to" includes the numerical values ​​recorded before and after "to" as the range of lower limit and upper limit. (Meth)acrylic acid refers to acrylic acid and methacrylic acid. In addition, with respect to the various components appearing in this specification, unless otherwise specified, they can be used alone independently, or two or more can be used in combination.

[0030] [Form of sealing sheet]

[0031] like Figure 1A As shown, the sealing sheet of the present disclosure is sequentially provided with a resin composition layer 2 and a protective film 3. A plurality of resin composition layers 2 may be provided. The protective film 3 is preferably directly laminated with the resin composition layer.

[0032] The protective film is a support for the resin composition layer and provides the sealing sheet with handleability. The protective film is preferably used in a form in which it is peeled off after forming a sealing layer around the optical semiconductor element using the resin composition layer.

[0033] In the above-mentioned usage form, the protective film is not particularly limited, and examples thereof include plastic films such as polyester films such as polybutylene terephthalate and polyethylene naphthalate, polyolefin films such as polypropylene and polyethylene, polyvinyl chloride films, polyurethane films, nylon films, polyolefin films, triacetyl cellulose films, and cycloolefin films.

[0034] The plastic film is preferably releasable, and more preferably a release layer is provided by coating a release agent such as silicone resin, alkyd resin, fluororesin, or melamine resin on the plastic film. The plastic film may also have a functional layer in addition to the release layer. Specifically, the functional layer includes an antistatic layer, and examples of the laminated structure include: antistatic layer / plastic film substrate / release layer, and plastic film substrate / antistatic layer / release layer.

[0035] The thickness Tb of the protective film (the thickness including the peeling layer when a peeling layer is provided) is not particularly limited, and is preferably 10 μm to 188 μm, more preferably 10 μm to 100 μm, and further preferably 10 μm to 75 μm. By setting it to 10 μm to 188 μm, the transfer of the corrugation of the protective film to the resin composition layer is controlled, and the embedding property and the adhesion become good. The thickness Tb can be measured, for example, by the method described in the examples described later.

[0036] When the protective film is directly laminated with the resin composition layer, the ratio of the root mean square height Sq of the surface roughness according to ISO 25178 to the thickness Ta of the resin composition layer in the surface of the protective film in contact with the resin composition layer is preferably 0.01% to 30%, more preferably 0.1% to 20%, and further preferably 0.15% to 12%. By setting it to 0.01% to 30%, the surface roughness transferred to the resin composition layer is controlled, and the resin composition layer is fully smoothed by the pressing process described later, thereby improving seamlessness and adhesion. The root mean square height Sq can be measured, for example, by the method described in the examples described later.

[0037] The root mean square height Sq value is preferably 0.01 μm to 2 μm, more preferably 0.04 μm to 1.5 μm, and even more preferably 0.1 μm to 1.5 μm.

[0038] In addition, the root mean square height Sq can be adjusted by the demoulding treatment of the peeling layer of the protective film. For example, it can be adjusted by the type of stripper, the coating amount of the stripper, and the coating method of the stripper. In the case of increasing the value of the root mean square height Sq, it is effective to reduce the coating amount of the stripper, speed up the drying after coating the stripper, and make the stripper contain fillers. In the case of reducing the value of the root mean square height Sq, it is sufficient to adjust it in the opposite way. In addition, a method of transferring the convex and concave using a film or carrier with a specified root mean square height Sq can also be applied.

[0039] like Figure 1B As shown, the sealing sheet disclosed in the present invention is more preferably a three-layer structure of protective film 3 / resin composition layer 2 / peeling liner 4. The peeling liner is a film with a peeling layer laminated on a substrate, and the substrate and peeling agent described in the protective film can be used. The same article can be used for the peeling liner and the protective film. Regarding the peeling force of the peeling liner 4, from the perspective of handling, it is preferably designed to be smaller than the protective film. The peeling force of the protective film 3 and the peeling liner 4 can be adjusted by the demoulding treatment of the surface of each peeling liner attached to the resin composition layer. For example, it can be adjusted by the type of peeling agent, the coating amount of the peeling agent, and the surface roughness of the peeling layer. In the case of wanting to reduce the value of the peeling force, it is effective to increase the coating amount of the peeling agent and other treatments. In the case of wanting to increase the value of the peeling force, it is only necessary to adjust it in the opposite way.

[0040] The thickness Tc of the release liner 4 is preferably in the range of 10 μm to 150 μm, and preferably satisfies the relationship of Tc<Tb.

[0041] In adopting Figure 1B In the case of the three-layer structure shown, a production method is preferably used in which the resin composition layer 2 is formed on the protective film 3 and then the release liner 4 is bonded thereto.

[0042] After manufacturing the sealing sheet, or while manufacturing the sealing sheet, the sealing sheet is wound around a core in a roll, thereby obtaining a sealing sheet roll. The length of the roll can be designed according to the purpose. From the perspective of improving productivity, it is preferably more than 50m, and more preferably more than 100m. From the perspective of manufacturing yield, the length of the roll is preferably set to 10,000m or less. In the case of making the sealing sheet into a roll form, it is preferred that the release liner is arranged outside the roll.

[0043] The sealing sheet disclosed in the present invention is used to seal the optical semiconductor element. The resin composition layer is preferably directly in close contact with the optical semiconductor element for sealing. The optical semiconductor element is not particularly limited, and is preferably arranged on a substrate such as acrylic, urethane, polycarbonate, epoxy, polyimide, glass, paper, cloth, aluminum, ceramic or polyethylene terephthalate, and has an electrode portion. The optical semiconductor element is arranged alone or in plurality. In the case where multiple optical semiconductor elements are arranged, a light shielding layer may also be provided between the optical semiconductor element portions.

[0044] Since the resin composition layer has a high followability to the concave and convex surface, it is suitable to follow the optical semiconductor element and fill the optical semiconductor element. A sealing layer comprising a resin composition layer is formed by filling the resin composition layer between the optical semiconductor elements. The sealing layer has the function of fixing the adjacent optical semiconductor elements and preventing them from falling off or shifting. In particular, the resin composition layer of the sealing sheet disclosed in the present invention can follow the micro-sized optical semiconductor elements, so micro-LEDs are more suitable as optical semiconductor elements, and it is preferred to use the resin composition layer as a sealing layer of a micro-LED display panel.

[0045] Micro LED refers to a fine LED element (chip) with a thickness of 50μm or 100μm or less. By mounting a plurality of such micro LEDs (chips) on a substrate with wiring or circuits, a display using a plurality of optical semiconductor elements as a light source is formed. Micro LEDs have LED elements such as GaAs, GaP, AlGaInP, and InGaN, and the operating temperature is 25°C to 60°C.

[0046] Below, use Figure 2 An example of the step of forming the sealing layer will be described.

[0047] Step (a): Sealing sheet placement step

[0048] like Figure 2 As shown in (a), the resin composition layer 2 of the sealing sheet is placed on the substrate 6 having the optical semiconductor element 5 so as to directly cover the optical semiconductor element 5. In addition, when the sealing sheet has a release liner, the release liner is peeled off to expose the resin composition layer 2, and then the sheet is placed as described above. The protective film may be peeled off immediately after placement, or may be peeled off after the pressing step shown below.

[0049] In this specification, the number of optical semiconductor elements is not particularly limited. In display applications, the number of optical semiconductor elements used is determined by the display size or the number of pixels.

[0050] The light emission color of the optical semiconductor element is not particularly limited, and examples of the light emission color include red, green, and blue. The size of the optical semiconductor element is preferably 100 μm or less in thickness and 40,000 μm in area when viewed from above. 2 The thickness is preferably 50 μm or less and the area is 10,000 μm in plan view. 2 The thickness is preferably 20 μm or less and the area is preferably 2,500 μm when viewed from above. 2 the following.

[0051] The spacing between the optical semiconductor elements mounted on the substrate is, for example, 10 μm to 5,000 μm. When red, green, and blue optical semiconductor elements are set as a group and mounted as one pixel on the substrate, the spacing between the pixels is, for example, 10 μm to 2,000 μm, preferably 20 μm to 1,800 μm, and more preferably 500 μm to 1,500 μm. The spacing between the optical semiconductor elements in one pixel is, for example, 10 μm to 200 μm, preferably 10 μm to 100 μm, and more preferably 20 μm to 60 μm.

[0052] Process (b): Pressing process

[0053] like Figure 2 As shown in (b), the resin composition layer 2 is made to flow by pressing and filled around the optical semiconductor element 5 or between the optical semiconductor elements 5. The resin composition layer 2 filled around the optical semiconductor element 5 or between the optical semiconductor elements 5 becomes a sealing layer 2'. The pressing method is not particularly limited, and hot pressing and vacuum pressing are preferred. From the perspective of the filling property of the resin composition layer, the temperature during pressing is preferably 20°C to 200°C, more preferably 30°C to 150°C, further preferably 40°C to 130°C, and particularly preferably 60°C to 110°C.

[0054] In order to improve the adhesion with optical semiconductor elements or adherends, heat aging may also be further performed after pressing. The heating temperature is preferably 40°C to 250°C, more preferably 80°C to 220°C, and more preferably 100°C to 190°C. The heating time is preferably 30 minutes to 300 minutes, more preferably 60 minutes to 240 minutes, and more preferably 90 minutes to 180 minutes. By setting the heating temperature and heating time, the residual stress of the resin composition layer can be removed and the close contact surface can be smoothed. Heat aging can also be implemented after step (c) described later.

[0055] Step (c): Etching step

[0056] In step (c), etching is performed to remove the sealing layer on the optical semiconductor element or to thin it. By removing the sealing layer, the brightness of the optical semiconductor element is improved and visibility during light emission is ensured. The thickness of the sealing layer after etching is preferably as follows: Figure 2 (c-1) is about the same thickness as the optical semiconductor element, or Figure 2 (c-2) indicates a thickness less than that of the optical semiconductor element. In addition, even if the sealing layer is not completely removed from the optical semiconductor element, it is sufficient to remove it substantially, and some thin film may remain. In addition, step (c) may be omitted if the brightness can be fully ensured.

[0057] The etching method is not particularly limited, and wet etching methods such as chemical polishing using a reagent, physical polishing using an abrasive, laser etching, plasma etching using argon plasma or oxygen plasma, and dry etching methods such as ion beam etching can be cited as preferred examples. From the perspective of reducing surface unevenness, plasma etching or a combination of wet etching and dry etching is preferred.

[0058] In addition, as the plasma etching conditions, for example, as long as CF 4 / O 2 / N 2 The mixed gas can be dry-etched at a power of 1500W to 3000W for 180 seconds to 600 seconds. 4 The gas supply amount can be, for example, 50 sccm to 100 sccm. 2 The gas supply rate can be set to 500 sccm to 1000 sccm, for example. 2 The gas supply amount can be, for example, set to 50 sccm to 100 sccm.

[0059] Through the above steps (a) to (c), a sealing layer can be formed from the resin composition layer.

[0060] Next, the constituent components of the sealing sheet of the present disclosure will be described in detail with reference to preferred examples.

[0061] [Resin composition layer]

[0062] The resin composition layer preferably contains resin (A) and metal oxide particles (B), and further contains a crosslinking agent and / or a polymerization initiator, and may also contain other components. As other components, for example, there are monomers and oligomers described later. In the present disclosure, resin (A) refers to a substance having the function of bonding and fixing objects as an adhesive. As a specific example, the function of bonding and fixing to a substrate having an optical semiconductor element or an optical semiconductor element can be cited.

[0063] The refractive index of the resin composition layer is 1.45 to 1.65, preferably 1.47 to 1.60, and more preferably 1.49 to 1.55. By setting the refractive index to 1.45 to 1.65, seamlessness and visibility are improved. The refractive index can be adjusted by the type or composition of the resin (A), the type, dispersion state or content of the metal oxide particles (B). The refractive index can be increased by increasing the content of the aromatic ring structure of the resin (A) and increasing the content of the metal oxide particles (B). If you want to reduce it, just adjust it in the opposite way. The content of the metal oxide particles (B) is preferably set to 5.3 to 48.2 parts by mass relative to 100 parts by mass of the total of the resin (A), the monomer and the oligomer.

[0064] The peak strength (tanδ peak strength) of the loss tangent (tanδ) of the resin composition layer disclosed in the present invention obtained by dynamic viscoelasticity measurement in the range of -50°C to 80°C refers to the value of the loss tangent (tanδ) when the tanδ curve becomes maximum, and when there are two or more peaks, it represents the peak strength on the lowest temperature side. The tanδ peak strength is preferably 0.6 to 2.2, more preferably 0.8 to 2.0, and further preferably 0.9 to 1.8. By setting the tanδ peak strength to 0.6 to 2.2, the absorbency of the pressure applied to the resin composition layer in the pressing process becomes good, a uniform sealing layer is formed and follows the optical semiconductor element, and the embedding property and adhesion are improved.

[0065] Furthermore, the tan δ peak intensity of the present disclosure can be adjusted by the type or composition of the resin (A), the type, dispersion state or content of the metal oxide particles (B), and the type or content of the monomer and / or oligomer.

[0066] Regarding the resin (A), when the resin (A) contains a (meth)acrylic resin (a), the tan δ peak intensity can be improved compared to when the resin (A) contains a urethane resin (b), but the present invention is not limited to this, depending on the resin composition. When the resin (A) contains a (meth)acrylic resin (a), the tan δ peak intensity can be reduced by increasing the content of alkyl methacrylate such as methyl methacrylate. When the tan δ peak intensity is to be increased, it is only necessary to adjust the opposite.

[0067] The metal oxide particles (B) contain ZrO 2 The situation with TiO 2 Compared with the case of the above, the tanδ peak intensity can be reduced, but it is not limited to this according to the dispersion state of the particles. 2 In the case of 2If the content of MgO is increased, the tanδ peak intensity can be reduced. If you want to increase the tanδ peak intensity, you only need to make the opposite adjustment.

[0068] When the resin composition layer contains monomers and / or oligomers, the tanδ peak intensity can be reduced by increasing the content of monomers and / or oligomers with low viscosity. When the tanδ peak intensity is to be increased, it is sufficient to adjust the content in the opposite direction. Specific examples of monomers with low viscosity include 1,6-hexanediol diacrylate, and specific examples of oligomers with low viscosity include oligomers with a weight average molecular weight of 1,300 or less.

[0069] In addition, the upper limit of the loss tangent (tan δ40) at 40°C obtained by dynamic viscoelasticity measurement of the resin composition layer of the present disclosure is preferably 2.2, more preferably 0.6 to 2.0, further preferably 0.8 to 1.9, and further preferably 1.0 to 1.8. By setting tan δ40 to 0.6 to 2.2, the pressure applied to the resin composition layer in the pressing process is appropriately diffused, and the embedding property and adhesion are improved.

[0070] In order to control the diffusibility of the pressure applied to the resin composition layer in the range of 20°C to 200°C, which is a preferred temperature band for the pressing process, the loss tangent at 40°C (tanδ40) is adjusted to 0.6 to 2.2, thereby achieving a balance between the loss tangent at 20°C to 40°C and the loss tangent at 40°C to 200°C without deviation.

[0071] The loss tangent (tan δ) is the ratio of loss elastic modulus / storage elastic modulus obtained by dynamic viscoelasticity measurement in a tensile mode at a frequency of 10 Hz and -50°C to 150°C. Tan δ40 can be adjusted by the type or composition of the resin (A) and the type or dispersion state of the metal oxide particles (B). Specifically, the same adjustment method as that for the tan δ peak intensity can be cited.

[0072] The dynamic viscoelasticity and loss tangent (tan δ) in the present disclosure are measured by the method described in the embodiments described later. In addition, when the resin composition layer includes any one of a photopolymerization initiator, a crosslinking agent, and a polymerization initiator, the crosslinking / polymerization reaction during the measurement is in an unfinished state. In addition, the measurement is preferably performed on a sheet with a thickness of 50 μm or more. In the case of measuring a sheet that does not meet the thickness, two groups of sealing sheets without a release liner can also be prepared, and the resin composition layers are bonded to each other using a laminator to prepare a laminate of a protective film / resin composition layer / protective film, and then the protective film on one side of the laminate is peeled off, and the resin composition layer of the sealing sheet is repeatedly bonded, thereby being laminated to become more than 50 μm, and then the dynamic viscoelasticity is measured.

[0073] From the viewpoint of embedding and adhesion, the thickness Ta of the resin composition layer is preferably 1 μm to 100 μm, more preferably 5 μm to 50 μm, and further preferably 5 μm to 30 μm. By setting the thickness Ta of the resin composition layer to 1 μm to 100 μm, the pressure is appropriately diffused and fully smoothed in the resin composition layer during the pressing process, so that embedding and adhesion are improved. The resin composition layer may be a single layer or any form of stacking of more than two layers. The thickness Ta in the present disclosure is measured by the method described in the embodiments described later.

[0074] CIE L of the resin composition layer * a * b * Chroma C in color space * It is preferably 0-10, more preferably 0-5, and still more preferably 0-3.

[0075] Chroma C * It is one of the indicators that indicate the vividness of hue, and is based on the chromaticity a * and b * The value obtained by the following formula 1.

[0076] C * =(a *2 +b *2 ) 0.5 (Formula 1)

[0077] In formula 1, C * is the chroma, a * and b * Chroma a * and b * , are all values ​​measured according to Japanese Industrial Standards (JIS) Z 8781-4. * By setting the value to 0 to 10, the influence of the color tone of the coating film on the color tone of the optical semiconductor is suppressed, and the seamlessness and visibility are improved.

[0078] Chroma C in this disclosure * The chroma C in this disclosure is measured by the method described in the examples below. * The chromaticity C can be adjusted by the type of resin (A), the type or content of metal oxide particles (B), the type or content of monomers and / or oligomers. When the resin (A) contains a (meth)acrylic resin (a), the chromaticity C can be increased by increasing the content of the functional group-containing monomer constituting the (meth)acrylic resin (a). * If you want to reduce it, just adjust it in the opposite way. If you increase the content of metal oxide particles (B), the chroma C can be increased.* , if you want to reduce the color saturation C * In the case where the resin composition layer contains monomers and / or oligomers, the chroma C can be increased by increasing the number of functional groups of the monomers or increasing the content of the functional group-containing monomers constituting the oligomers. * If you want to lower it, just adjust it in the opposite direction.

[0079] The haze of the resin composition layer is preferably 12% or less, more preferably 8% or less, and still more preferably 5% or less. The haze in the present disclosure is measured by the method of Examples described later.

[0080] The total light transmittance of the resin composition layer is preferably 80% or more, more preferably 85% or more, and still more preferably 90% or more. The total light transmittance of the resin composition layer is measured by the method described in Examples below.

[0081] By setting the haze and total light transmittance of the resin composition layer to the above range, the scattering of light passing through the sealing layer is reduced, and the seamlessness and visibility are improved. The haze and total light transmittance of the resin composition layer in the present disclosure can be adjusted by the type of resin (A), or the type, dispersion state or content of metal oxide particles (B), and the type or content of monomers and / or oligomers. In the case of containing (meth) acrylic resin (a) as resin (A), or in the case of containing ZrO 2 In the case of metal oxide particles (B), the haze and the total light transmittance can be reduced.

[0082] [Method for forming resin composition layer]

[0083] The method for forming the resin composition layer is not particularly limited, and a suitable example is a method of coating a resin composition obtained by adding an arbitrary solvent to the components constituting the resin composition layer. The purpose of adding the solvent is to adjust the viscosity to a level suitable for coating.

[0084] For coating, known coating machines or methods such as notch wheel coater, die coater, roll coater, die lip coater, reverse coater, gravure coater, rod coater, curtain coater, dip coating, spin coating, screen coating, and casting can be used. The solvent contained in the resin composition can be removed by a drying process after coating.

[0085] As a preferred embodiment, the resin composition can be applied to a support such as a protective film, a release liner, etc., and then the coated film is heated and dried using a hot air oven, an infrared heater, etc., thereby forming a resin composition layer on one side of the support. Furthermore, in order to improve the crosslinking density of the resin composition layer, it is preferably subjected to an aging treatment such as standing at a specific temperature, or irradiated with ultraviolet light (ultraviolet, UV), etc. In addition, it can also be transferred to other supports such as a protective film, a release liner, a substrate, etc. using a laminator after coating.

[0086] [Resin composition]

[0087] The resin composition can be obtained by stirring and mixing a solvent, a resin (A) and metal oxide particles (B). Any solvent is used for the purpose of adjusting the processing suitability such as viscosity when mixing the resin (A) with the metal oxide particles (B), so esters, ether esters, ethers, alcohols, aromatics, etc. that are compatible with the resin (A) can be used appropriately. Specifically, acetone, 2-butanone, ethyl acetate, cyclohexanone, toluene, xylene, isopropanol, N-methyl-2-pyrrolidone, etc. can be cited as suitable examples. A known stirring device can be used for stirring, preferably a disperser, a mixer, an oscillator, a homogenizer, etc.

[0088] In order to obtain the resin composition, the following manufacturing process can be adopted: first, a mixture of metal oxide particles (B) mixed with resin (A) or any solvent is prepared, and second, a two-stage or more manufacturing process of adding resin (A), a crosslinking agent, a polymerization initiator, and other components as needed.

[0089] [Resin (A)]

[0090] The weight average molecular weight (Mw) of the resin (A) is preferably 10,000 to 1,000,000. From the viewpoint of light resistance and adhesion, it is more preferably 20,000 to 300,000, and further preferably 30,000 to 150,000. By setting the weight average molecular weight (Mw) to 10,000 to 1,000,000, the entanglement of the molecular chains in the heat aging process is easily untangled, and the adhesion is improved.

[0091] In addition, the ratio (Mw / Mn) of the number average molecular weight (Mn) to the weight average molecular weight (Mw) indicating the dispersion degree of the resin (A) is preferably 1 to 5, more preferably 2 to 4.5, and further preferably 2.5 to 4. By setting Mw / Mn to 1 to 5, the flow rate when the resin is heated is made uniform within the resin, so that the fluidity of the resin is easily controlled and the embedding property is improved. In addition, since the speed of wetting the adherend is also uniform, the adhesion is improved.

[0092] In addition, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-equivalent values ​​measured by gel permeation chromatography (GPC). The weight average molecular weight (Mw) and the number average molecular weight (Mn) in the present disclosure are measured by the method described in the Examples described below.

[0093] The glass transition temperature (Tg) of the resin (A) is -30°C to 60°C. From the viewpoint of embedding property and adhesion, it is more preferably -20°C to 50°C, further preferably -15°C to 40°C, further preferably -10°C to 30°C, and particularly preferably 0°C to 20°C. By setting the glass transition temperature (Tg) to -30°C or higher, the fluidity or wettability of the resin (A) in the pressing step can be made appropriate, and the embedding property or adhesion can be improved.

[0094] By setting the glass transition temperature (Tg) to 60°C or less, when pressure is applied to the resin composition layer in the pressing step, the molecular motion of the resin (A) contained in the resin composition layer is activated, and the molecular chain entanglement is easily untangled. If the molecular chain entanglement is untangled, it can deform in a manner following the uneven adherend such as a substrate or an optical semiconductor element, and the gap between the optical semiconductor element and the resin composition layer can be reduced, thereby improving embedding properties.

[0095] The glass transition temperature (Tg) of the resin (A) in the present disclosure refers to the glass transition temperature (Tg) before thermal crosslinking and before photocrosslinking when the resin (A) undergoes a crosslinking reaction caused by heat or light. The glass transition temperature (Tg) of the resin (A) in the present disclosure is measured by the method described in the examples described below.

[0096] Resin (A) can be used alone or in combination of two or more. Based on the total amount (100% by mass) of the resin composition layer, the content of resin (A) is preferably 10% by mass to 98% by mass, more preferably 40% by mass to 95% by mass, and further preferably 60% by mass to 90% by mass. In the case of comprising two or more resins (A), the content of any resin (A) is preferably 5% by mass or more, and the total content is preferably in the range. By setting the content of resin (A) to 10% by mass to 98% by mass, the compatibility with metal oxide particles (B) becomes good, and visibility improves.

[0097] Preferred examples of the resin (A) include (meth)acrylic resins (a), urethane resins (b) such as polyurethane resins or polyurethane urea resins, maleic acid resins, styrene-maleic acid copolymers, polystyrene resins, polybutadiene resins, polyester resins, condensation-type polyester resins, addition-type polyester resins, melamine resins, epoxy resins, polycarbonate resins, oxetane resins, phenoxy resins, polyimide resins, polyamideimide resins, alkyd resins, amino resins, polyamide resins, polylactic acid resins, oxazoline resins, benzoxazine resins, silicone resins, fluororesins, butyral resins, chlorinated polyethylene, chlorinated polypropylene, polyvinyl chloride, vinyl chloride-vinyl acetate copolymers, polyvinyl acetate, vinyl-based resins, rubber-based resins, cyclized rubber-based resins, celluloses, polyethylene (high-density polyethylene (HDPE), low-density polyethylene (LDPE)), and the like. From the viewpoint of embedding properties, it is preferred that at least one of the (meth)acrylic resin (a) and the urethane resin (b) is contained. Furthermore, from the viewpoint of adhesion, it is more preferred that the (meth)acrylic resin (a) is contained.

[0098] The resin (A) preferably has a plurality of functional groups that can be used for crosslinking reaction by heat or light. The functional group can be appropriately selected according to the combination with the crosslinking agent, thermal polymerization initiator, and photopolymerization initiator described below, and may be a self-crosslinkable functional group.

[0099] Examples of the functional group include a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an oxetanyl group, an oxazoline group, an oxazine group, an aziridine group, a thiol group, an isocyanate group, a blocked isocyanate group, a silanol group, a vinyl group, and an acryloyl group.

[0100] From the viewpoint of the dispersibility of the metal oxide particles (B), carboxyl, hydroxyl, and epoxy groups are preferred. In the case of having a carboxyl group, the acid value of the resin (A) is preferably 1 mgKOH / g to 45 mgKOH / g, more preferably 3 mgKOH / g to 30 mgKOH / g, and further preferably 5 mgKOH / g to 20 mgKOH / g. By setting the acid value of the resin (A) to 1 mgKOH / g to 45 mgKOH / g, the crosslinking density with the crosslinking agent can be optimized to improve the adhesion. The acid value in the present disclosure is measured by the method described in the examples described later.

[0101] When the crosslinking reaction is induced by light, the resin (A) preferably has one or more unsaturated bonds in one molecule and preferably also contains a photopolymerization initiator.

[0102] Examples of the photopolymerization initiator include triazine-based photopolymerization initiators, borate-based photopolymerization initiators, carbazole-based photopolymerization initiators, acetophenone-based photopolymerization initiators, and oxime-ester-based photopolymerization initiators. Acetophenone-based photopolymerization initiators and oxime-ester-based photopolymerization initiators are preferred because they are less yellowed during the heat aging process.

[0103] From the viewpoint of yellowing, the content of the photopolymerization initiator is preferably 0.5 to 10% by mass, more preferably 0.5 to 5% by mass, based on the total amount (100% by mass) of the resin composition layer.

[0104] When the crosslinking reaction is induced by heat, preferred embodiments include the first embodiment in which the crosslinking reaction is combined with a crosslinking agent and the second embodiment in which the crosslinking reaction is combined with a thermal polymerization initiator.

[0105] [(Meth)acrylic resin (a)]

[0106] In the present disclosure, the (meth)acrylic resin (a) is an acrylic copolymer (polymer) obtained by copolymerizing monomers containing (meth)acrylic acid ester monomers, and is a polymer having constituent units based on 25 to 20,000 monomers, and the weight average molecular weight of the (meth)acrylic resin (a) is 10,000 to 1,000,000. As a suitable example of the (meth)acrylic acid ester monomer, an alkyl (meth)acrylic acid ester monomer can be exemplified. In the case of forming a cross-linked structure, a (meth)acrylic acid copolymer obtained by copolymerizing a functional group-containing monomer with a (meth)acrylic acid ester monomer is preferred.

[0107] The (meth)acrylic acid alkyl ester monomer is a compound obtained by esterifying (meth)acrylic acid and introducing an alkyl group or a cycloalkyl group, and the alkyl group or the cycloalkyl group may be any of a linear, branched, or cyclic saturated aliphatic hydrocarbon group. The saturated aliphatic hydrocarbon group is preferably a saturated aliphatic hydrocarbon group having 1 to 20 carbon atoms, and more preferably a saturated aliphatic hydrocarbon group having 1 to 12 carbon atoms. Specific examples thereof include: methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, and (meth)acrylate. The present invention also provides the following esters: isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, lauryl (meth)acrylate, cyclohexyl (meth)acrylate, 4-n-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, etc. Among these, methyl (meth)acrylate, n-butyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and lauryl (meth)acrylate are particularly preferably used from the viewpoint of the dispersibility of the metal oxide particles (B), and methyl (meth)acrylate and n-butyl (meth)acrylate are particularly preferably used.

[0108] From the viewpoint of adhesion, the content of the structural unit derived from the alkyl (meth)acrylate monomer is preferably 1 to 100 mass %, more preferably 20 to 99.9 mass %, and even more preferably 80 to 99.7 % based on 100 mass % of the (meth)acrylic resin (a).

[0109] The (meth)acrylic resin (a) preferably has a structural unit derived from a functional group-containing monomer and / or an unsaturated bond.

[0110] As the monomer containing a functional group, there can be exemplified carboxyl-containing monomers, hydroxyl-containing monomers, epoxy-containing monomers, and amino-containing monomers. By containing a monomer containing a functional group, the cohesive force of the resin (A) is improved, and a tough resin composition layer can be obtained. Particularly preferred are monomers containing carboxyl-containing monomers, hydroxyl-containing monomers, and epoxy-containing monomers.

[0111] Examples of carboxyl group-containing monomers include (meth)acrylic acid, β-carboxyethyl (meth)acrylate, p-carboxybenzyl (meth)acrylate, carboxypentyl (meth)acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, citraconic acid, and isocrotonic acid. Among these, (meth)acrylic acid is preferred from the viewpoint of adhesion.

[0112] Examples of hydroxyl-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Among these, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are more preferred from the viewpoint of adhesion.

[0113] Examples of the epoxy group-containing monomer include glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and 6-methyl-3,4-epoxycyclohexylmethyl (meth)acrylate. Among these, glycidyl (meth)acrylate is preferably contained from the viewpoint of adhesion.

[0114] Examples of the amino group-containing monomer include monoalkylamino (meth)acrylates such as monomethylaminoethyl (meth)acrylate, monoethylaminoethyl (meth)acrylate, monomethylaminopropyl (meth)acrylate, and monoethylaminopropyl (meth)acrylate.

[0115] The total amount of the structural units derived from the functional group-containing monomer is preferably 0.1 to 20% by mass relative to 100% by mass of the (meth)acrylic resin (a). By setting the content within the above range, the cohesive force can be adjusted by the reaction with the crosslinking agent.

[0116] The content of the structural unit derived from the carboxyl group-containing monomer is preferably 0.1% by mass to 10% by mass based on 100% by mass of the (meth)acrylic resin (a). By being within the above range, the adhesion can be improved.

[0117] The content of the structural unit derived from the hydroxyl group-containing monomer is preferably 0.1% to 10% by mass based on 100% by mass of the (meth)acrylic resin (a). By being within the above range, the adhesion can be improved.

[0118] The content of the structural unit derived from the epoxy group-containing monomer is preferably 0.1% to 15% by mass based on 100% by mass of the (meth)acrylic resin (a). By being within the above range, the adhesion can be improved.

[0119] As a further preferred example of the functional group-containing monomer constituting the (meth)acrylic resin (a), a monomer containing a carboxyl group and a monomer containing a hydroxyl group may be mentioned. By not containing a carboxyl group-containing monomer and a hydroxyl group-containing monomer at the same time, the cohesive force of the (meth)acrylic resin (a) can be adjusted and the adhesion can be improved.

[0120] The (meth)acrylic resin (a) may also contain structural units derived from other monomers that can be copolymerized with the (meth)acrylic acid alkyl ester and the functional group-containing monomer. For example, monomers having an alkylene oxide group and other vinyl monomers can be cited. For example, methoxyethyl acrylate, methoxydiethylene glycol acrylate, vinyl acetate, crotonic acid vinyl ester, styrene, acrylonitrile, and acrylamide can be illustrated. The structural units derived from the other monomers are preferably 0.1% to 20% by mass in 100% by mass of the (meth)acrylic acid copolymer.

[0121] (Meth) acrylic resin (a) can be obtained by polymerizing an acrylic monomer mixture. During polymerization, a polymerization initiator can be used as needed. The content of the polymerization initiator is set to, for example, 0.01% to 10% by mass relative to 100% by mass of the monomer mixture. The polymerization method is not limited. For example, polymerization can be carried out by solution polymerization, block polymerization, emulsion polymerization, and suspension polymerization. In terms of the ease of polymerization control, solution polymerization is particularly preferred. The solvent used in the solution polymerization can be exemplified by: acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone. The polymerization temperature can be set to, for example, about 60°C to 120°C, and the polymerization time can be set to about 2 hours to 12 hours.

[0122] The polymerization initiator is preferably a free radical polymerization initiator. As the free radical polymerization initiator, peroxides and azo compounds are suitable. Any of the thermal free radical polymerization initiators described below can be used, and specifically, 2,2'-azobisisobutyronitrile (abbreviation: AIBN (2,2'-azobisisobutyronitrile)) is preferred.

[0123] [Urethane resin (b)]

[0124] In the present disclosure, the urethane resin (b) is a general term for compounds containing two or more urethane bonds in one molecule. The urethane resin can be obtained by reacting polyisocyanate with polyol.

[0125] As long as the polyisocyanate has two or more isocyanate groups in one molecule, it is preferably a diisocyanate or a triisocyanate, and more preferably a diisocyanate in terms of the dispersibility of the metal oxide particles (B). As the diisocyanate, it can be appropriately selected from known aliphatic diisocyanates such as hexamethylene diisocyanate or known aromatic diisocyanates such as benzene-1,3-diisocyanate. In addition, an isocyanate-terminated prepolymer obtained by reacting a polyol with an excess of polyisocyanate can also be used as an intermediate of the urethane resin.

[0126] The polyol may be any substance having two or more hydroxyl groups in one molecule, and is preferably a diol or a triol, more preferably a diol, from the perspective of the dispersibility of the metal oxide particles (B). As the diol, it can be appropriately selected from known aliphatic diols such as ethylene glycol or known aromatic diols such as benzene glycol. In addition, prepolymers such as polyether polyols, polyester polyols, and polycarbonate polyols can also be used.

[0127] The urethane resin (b) may be a polyurethane urea resin having a urea bond. The polyurethane urea resin can be synthesized by reacting, for example, a polyamine with a urethane resin having an isocyanate group at the terminal.

[0128] The polyamine may be any substance having two or more amino groups in one molecule, and is preferably a diamine or a triamine, and more preferably a diamine, from the perspective of the dispersibility of the metal oxide particles (B). The diamine may be appropriately selected from known aliphatic diamines such as ethylenediamine or known aromatic diamines such as phenylenediamine.

[0129] [Metal oxide particles (B)]

[0130] In the present embodiment, the metal oxide particles (B) have the function of improving the fluidity of the resin (A) and improving embedding properties between optical semiconductor elements, and also have the function of adjusting the refractive index.

[0131] Examples of the metal constituting the metal oxide particles (B) include Ti, Al, Zr, In, Zn, Sn, La, Y, Ce, Mg, Hf, Ta, Ba, Ca, and Si. From the viewpoint of improving embedding properties and seamless properties, Ti, Al, and Zr are preferred, and Zr is more preferred. The metal oxide particles (B) may be used alone or in combination of two or more.

[0132] Examples of the metal oxide particles (B) containing Ti include titanium monoxide (TiO), titanium dioxide (TiO 2 ), titanium trioxide (TiO 3 ), barium titanate (BaTiO 3), perovskite (CaTiO 3 ).

[0133] Examples of the metal oxide particles (B) containing Al include aluminum oxide (Al 2 O 3 ), spinel (MgAl 2 O 4 ).

[0134] Examples of the metal oxide particles (B) containing Zr include zirconium oxide (ZrO 2 ).

[0135] Among these, aluminum oxide (Al 2 O 3 ), titanium dioxide (TiO 2 )、ZrO 2 ), particularly preferably zirconium oxide (ZrO 2 ).

[0136] As metal oxide particles (B) other than those mentioned above, indium oxide (In 2 O 3 )、ZnO、SnO 2 ), lanthanum oxide (La 2 O 3 ), yttrium oxide (Y 2 O 3 ), cerium oxide (CeO 2 ), magnesium oxide (MgO), hafnium oxide (HfO 2 ), Tantalum pentoxide (Ta 2 O 5 ), niobium pentoxide (Nb 2 O 5 ), silicon dioxide (SiO 2 ), indium tin oxide (ITO), antimony tin oxide (ATO), etc.

[0137] The metal oxide particles (B) are preferably metal oxide particles whose surfaces are modified by a surface modifier. Examples of the surface modifier include organic acids, silane coupling agents, surfactants, titanium coupling agents, and metal impurities, and preferably contain organic acids.

[0138] From the viewpoint of dispersibility, the specific surface area of ​​the metal oxide particles (B) obtained by the Brunauer-Emmett-Teller (BET) method is preferably 10 m 2 / g~400m 2 / g, more preferably 10m2 / g~150m 2 / g, and more preferably 20m 2 / g~84m 2 The specific surface area obtained by the BET method can be measured in accordance with JIS Z 8830.

[0139] The number average primary particle diameter of the metal oxide particles (B) is 5nm to 50nm, preferably 5nm to 30nm, more preferably 7nm to 25nm, and particularly preferably 10nm to 20nm. By setting it to 5nm to 50nm, the fluidity of the resin composition layer becomes good and the embedding property is improved. In addition, it is easy to maintain the viscosity of the resin composition at a level suitable for coating. Furthermore, the dispersibility in the resin becomes good, and the refractive index adjustment function is easily manifested.

[0140] The number average primary particle diameter of the metal oxide particles (B) can be determined as follows: the metal oxide particles (B) are magnified to about 50,000 to 1,000,000 times using a transmission electron microscope (TEM), a field emission transmission electron microscope (FE-TEM), a field emission scanning electron microscope (FE-SEM), etc. to obtain an image, and 20 particles that can be observed in the image are randomly selected, and the lengths of the particles in the long axis direction are measured to obtain the arithmetic average.

[0141] The content of the metal oxide particles (B) is preferably 1% to 40% by mass, more preferably 3% to 35% by mass, and further preferably 5% to 30% by mass, based on the total amount (100% by mass) of the resin composition layer. The reason is that by setting the content to 1% to 40% by mass, the flow of the resin composition becomes suitable and the embedding property becomes excellent. In addition, the dispersibility in the resin becomes suitable and the visibility is improved.

[0142] From the viewpoint of adjusting the loss tangent (tan δ) and embedding property of the resin composition layer, it is preferred that the metal oxide particles (B) are dispersed in the resin (A) and used as a metal oxide particle dispersion. As a dispersion treatment, the disperser used in the mechanical crushing can be any disperser as long as it is a generally used disperser, and examples thereof include: a ball mill, a roller mill, a sand mill, a bead mill, and a nano homogenizer. Among them, a bead mill is preferably used. As such a disperser, for example, a super mill, a sand grinder, an agitator mill, a grain mill, a dyno-mill, a pearl mill, and a cobol mill (all trade names) can be listed.

[0143] In the present disclosure, from the viewpoint of storage stability of the resin composition layer, it is preferred to use a dispersant in the dispersion treatment of the metal oxide particles (B). In the present disclosure, the dispersant has a function of imparting repulsion between particles to prevent the particles that have been divided by the dispersion treatment from reaggregating.

[0144] As the dispersant, a conventionally known compound can be used, and examples thereof include cationic, anionic or nonionic surfactants, cationic, anionic or nonionic polymer dispersants, and pigment derivative-type dispersants.

[0145] Examples of the polymer dispersant include polyurethane resins, polyester resins, polyamide resins, (meth)acrylic resins, polycarboxylates (salts), styrene copolymers, polyalkylene oxide derivatives, and phosphate resins.

[0146] The acid value of the polymer dispersant is preferably 5 mgKOH / g to 450 mgKOH / g, more preferably 46 mgKOH / g to 300 mgKOH / g, and further preferably 50 mgKOH / g to 200 mgKOH / g. If the acid value is moderate, an excellent electrostatic repulsion effect can be obtained, and a dispersion having excellent storage stability can be obtained. The acid value in the present disclosure is measured by the method described in the examples described later.

[0147] The weight average molecular weight (Mw) of the polymer dispersant is preferably 1,000 to 50,000, more preferably 3,000 to 30,000. If the weight average molecular weight (Mw) is appropriate, the adsorption rate of the colorant is improved, and a dispersion with excellent stability can be obtained. The weight average molecular weight (Mw) in the present disclosure is measured by the method described in the examples described later.

[0148] Pigment derivative dispersants are compounds having acidic groups, basic groups, neutral groups, etc. in organic pigment residues. For example, compounds having acidic substituents such as sulfonic groups, carboxyl groups or phosphoric acid groups, and amine salts thereof, compounds having basic substituents such as sulfonyl groups, amide groups or terminal tertiary amino groups, and compounds having neutral substituents such as phenyl or phthalimide alkyl groups. Organic pigments, for example, can be listed as phthalocyanine pigments, diketopyrrolopyrrole pigments, anthraquinone pigments, quinacridone pigments, dioxazine pigments, perylene pigments, thiazine indigo pigments, triazine pigments, benzimidazolone pigments, indole pigments such as benzisoindole, isoindoline pigments, isoindoline ketone pigments, quinophthalone pigments, naphthol pigments, reduction (threne) pigments, metal complex pigments, azo, disazo, polyazo and other azo pigments.

[0149] These dispersants may be used alone or in combination of two or more. By using these dispersants, the metal oxide particles (B) contained in the resin composition layer can be prevented from aggregating over time, thereby preventing unevenness of the sealing sheet.

[0150] The content of the dispersant (the total content when two or more are included) is preferably 0.01% to 10% by mass, and more preferably 0.1% to 5% by mass, based on the total amount (100% by mass) of the resin composition layer. By containing 0.01% by mass or more of the dispersant, the cohesiveness of the resin composition layer over time becomes good, and by being 10% by mass or less, the viscosity of the metal oxide particle (B) dispersion falls within an appropriate range, and the coating suitability becomes good.

[0151] [First embodiment]

[0152] In the first embodiment of the present disclosure, the resin composition layer comprises a resin (A) and a crosslinking agent. The first embodiment is characterized in that the functional group of the resin (A) reacts with the crosslinking agent by heating the resin composition layer, thereby forming a crosslinked structure. From the perspective of coating film strength, the resin (A) is preferably the resin (A) having a weight average molecular weight (Mw) of 10,000 or more, and more preferably the (meth) acrylic resin (a).

[0153] [Crosslinking agent]

[0154] In the first embodiment, in order to promote the formation of a cross-linked structure, the resin composition layer of the present disclosure preferably contains a cross-linking agent. The cross-linking agent can be used alone or in combination of two or more. The cross-linking agent undergoes a cross-linking reaction with the reactive functional group of the resin (A) during hot pressing or heat aging in the pressing process, thereby increasing the cohesive force of the resin composition layer and improving the adhesion.

[0155] The crosslinking agent has a plurality of functional groups that can react with the functional groups of the resin (A). Examples of the crosslinking agent include known compounds such as silane coupling agents, epoxy crosslinking agents, acid anhydride group-containing compounds, imidazole compounds, isocyanate compounds, aziridine compounds, and amine compounds. From the perspective of adjusting the loss tangent (tan δ) of the resin composition layer, preferably, a silane coupling agent, an epoxy crosslinking agent, an aziridine compound, an imidazole compound, and an isocyanate compound are used, and from the perspective of adhesion, an epoxy crosslinking agent is more preferred.

[0156] The silane coupling agent is a compound in which a hydrolyzable group such as a methoxy group or an ethoxy group and a functional group such as an epoxy group are bonded to a Si atom via an alkylene group.

[0157] Examples of the silane coupling agent include alkoxysilane compounds having a (meth)acryloxy group such as 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltributoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, and 3-(meth)acryloxypropylmethyldiethoxysilane;

[0158] Alkoxysilane compounds having a vinyl group, such as vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriisopropoxysilane, vinyltributoxysilane, vinylmethyldimethoxysilane, and vinylmethyldiethoxysilane;

[0159] Alkoxysilane compounds having an amino group such as 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltripropoxysilane, 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, and N-phenyl-3-aminopropyltrimethoxysilane; alkoxysilane compounds having a mercapto group such as 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyltripropoxysilane, 3-mercaptopropylmethyldimethoxysilane, and 3-mercaptopropylmethyldiethoxysilane;

[0160] Alkoxysilane compounds having an epoxy group, such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltripropoxysilane, 3-glycidoxypropyltributoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane;

[0161] Tetraalkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetrabutoxysilane;

[0162] 3-Chloropropyltrimethoxysilane, n-hexyltrimethoxysilane, n-hexyltriethoxysilane, n-decyltrimethoxysilane, n-decyltriethoxysilane, styryltrimethoxysilane, phenyltrimethoxysilane, diphenyldimethoxysilane, 3-triethoxysilyl-N-(1,3-dimethylbutylene)propylamine, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, hexamethyldisilazane, silicone resin having an alkoxysilyl group in the molecule, etc. From the viewpoint of adhesion, an alkoxysilane compound is preferred, and 3-glycidyloxypropyltrimethoxysilane is more preferred.

[0163] The epoxy crosslinking agent is a compound having two or more epoxy groups in one molecule, and is a compound other than the (meth)acrylic resin (a) having the epoxy-containing monomer. As the properties of the epoxy crosslinking agent, by using a liquid form, the tanδ peak temperature of the resin composition layer can be reduced, and the optical semiconductor element and the resin composition layer can be well adhered. On the other hand, by using a solid form, the tanδ peak temperature of the resin composition layer can be increased, the stickiness of the resin composition layer can be controlled, and the seamlessness can be adjusted.

[0164] Examples of the epoxy crosslinking agent include glycidyl ether epoxy crosslinking agents, glycidyl amine epoxy crosslinking agents, glycidyl ester epoxy crosslinking agents, cyclic aliphatic (alicyclic) epoxy crosslinking agents, bisphenol epoxy crosslinking agents, hydrogenated bisphenol epoxy crosslinking agents, and the like. From the viewpoint of adhesion, bisphenol epoxy crosslinking agents and hydrogenated bisphenol epoxy crosslinking agents are preferred.

[0165] Examples of the glycidyl ether epoxy crosslinking agent include a cresol novolac epoxy crosslinking agent, tris(glycidyloxyphenyl)methane, and tetrakis(glycidyloxyphenyl)ethane.

[0166] Examples of the glycidylamine type epoxy crosslinking agent include tetraglycidyldiaminodiphenylmethane and tetraglycidylmeta-xylylenediamine.

[0167] Examples of the glycidyl ester type epoxy crosslinking agent include diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate.

[0168] Examples of the cycloaliphatic (alicyclic) epoxy crosslinking agent include epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl) adipate.

[0169] Examples of the bisphenol epoxy crosslinking agent include bisphenol A epoxy crosslinking agents, bisphenol F epoxy crosslinking agents, bisphenol S epoxy crosslinking agents, and bisphenol AD ​​epoxy crosslinking agents. From the viewpoint of adhesion, bisphenol A epoxy crosslinking agents are particularly preferred.

[0170] Examples of the hydrogenated bisphenol epoxy crosslinking agent include hydrogenated bisphenol A epoxy crosslinking agents and hydrogenated bisphenol F epoxy crosslinking agents. In terms of adhesion, hydrogenated bisphenol A epoxy crosslinking agents are particularly preferred.

[0171] Examples of the aziridine compound include trimethylolpropane-tris-β-aziridinyl propionate, tetramethylolmethane-tris-β-aziridinyl propionate, N,N'-diphenylmethane-4,4'-bis(1-aziridinecarboxamide), N,N'-hexamethylene-1,6-bis(1-aziridinecarboxamide), tris-2,4,6-(1-aziridinyl)-1,3,5-triazine, and 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane.

[0172] Examples of the imidazole compound include 2-methylimidazole, 2-phenyl-4-methylimidazole, 2,4-dimethylimidazole, 2-phenylimidazole, imidazole, 2-undecylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazolium trimellitic acid, 2,4-diamino-6-[2'-methylimidazolyl-(1') ]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole and the like, and further examples include compounds having improved storage stability such as a type in which the imidazole compound is reacted with an epoxy resin and becomes insoluble in a solvent, and a type in which the imidazole compound is encapsulated in a microcapsule.

[0173] The isocyanate compound is an isocyanate having two or more isocyanate groups and is preferably an isocyanate monomer such as aromatic polyisocyanate, aliphatic polyisocyanate, aromatic aliphatic polyisocyanate, alicyclic polyisocyanate, and a biuret form, urate form, and adduct thereof.

[0174] Examples of the aromatic polyisocyanate include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanatotoluene, 1,3,5-triisocyanatobenzene, bimanisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate. From the viewpoint of adhesion, 2,4-toluene diisocyanate is preferred.

[0175] Examples of the aliphatic polyisocyanate include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HDI (hexamethylene diisocyanate)), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0176] Examples of the aromatic aliphatic polyisocyanate include ω,ω′-diisocyanate-1,3-dimethylbenzene, ω,ω′-diisocyanate-1,4-dimethylbenzene, ω,ω′-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0177] Examples of the alicyclic polyisocyanate include 3-isocyanate methyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI (isophorone diisocyanate), isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanate methyl)cyclohexane.

[0178] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer. Examples of the biuret form include a biuret form of hexamethylene diisocyanate.

[0179] The urate body is a trimer of an isocyanate monomer, and examples thereof include a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, and a trimer of toluene diisocyanate.

[0180] The adduct is a difunctional or higher isocyanate compound formed by reacting an isocyanate monomer with a difunctional or higher compound containing low molecular active hydrogen. Examples of the adduct include a compound formed by reacting trimethylolpropane with hexamethylene diisocyanate, a compound formed by reacting trimethylolpropane with toluene diisocyanate, a compound formed by reacting trimethylolpropane with xylylene diisocyanate, a compound formed by reacting trimethylolpropane with isophorone diisocyanate, and a compound formed by reacting 1,6-hexanediol with hexamethylene diisocyanate.

[0181] From the viewpoint of forming a sufficient cross-linked structure, the isocyanate compound is preferably a trifunctional isocyanate compound. The isocyanate compound is more preferably an adduct of a reaction product of an isocyanate monomer and a trifunctional compound containing low molecular active hydrogen, and a urate body. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a urate body of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, a urate body of toluene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, and a urate body of isophorone diisocyanate, more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of toluene diisocyanate, and a trimethylolpropane adduct of isophorone diisocyanate.

[0182] In the first embodiment, from the viewpoint of coating film strength, it is preferred to contain two or more crosslinking agents. From the viewpoint of adjusting the loss tangent (tan δ) of the resin composition layer, specifically, suitable examples include two or more selected from silane coupling agents, epoxy crosslinking agents, aziridine compounds, and isocyanate compounds.

[0183] The content of the crosslinking agent (the total content when two or more types are used in combination) is preferably 0.01% to 30% by mass, more preferably 0.05% to 20% by mass, and further preferably 0.1% to 10% by mass, based on the total amount (100% by mass) of the resin composition layer. By setting the content to the above, embedding property and adhesion can be appropriately adjusted.

[0184] [Cross-linking adjustment ingredients]

[0185] In order to adjust the crosslinking speed or the physical properties of the resin composition layer, the resin composition layer of the first embodiment preferably contains a crosslinking adjustment component such as a crosslinking accelerator or a crosslinking retarder. The crosslinking accelerator is not particularly limited and can be appropriately selected. As a specific example of the crosslinking accelerator, for example, phosphorus-based crosslinking accelerators, amine-based crosslinking accelerators, and guanidine-based crosslinking accelerators can be listed. These can be used alone or in combination of two or more.

[0186] From the viewpoint of coating suitability, the content of the crosslinking accelerator is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, based on the total amount (100% by mass) of the resin composition layer.

[0187] [Second embodiment]

[0188] In the second embodiment of the present disclosure, the resin composition layer contains a resin (A) and a thermal polymerization initiator. Furthermore, the resin composition layer preferably contains a monomer and / or an oligomer.

[0189] The second embodiment is characterized in that: by heating the resin composition layer, free radicals or ions (cations or anions) are generated from the thermal polymerization initiator, and a polymerization reaction is caused at the unsaturated bond site of any one of the resin (A), monomers, and oligomers, thereby making the resin composition layer high molecular weight. In the case where the resin composition layer contains monomers or oligomers, the resin (A) and the monomers and oligomers are sometimes bonded to each other. From the perspective of coating film strength, the resin (A) is preferably the resin (A) having a weight average molecular weight (Mw) of more than 10,000, and more preferably the (meth) acrylic resin (a).

[0190] [Thermal polymerization initiator]

[0191] In the present embodiment, as the thermal polymerization initiator, a thermal cationic polymerization initiator or a thermal free radical polymerization initiator can be used. From the viewpoint of the storage stability of the resin composition layer, a thermal free radical polymerization initiator is preferred. These can be used alone or in combination of two or more.

[0192] Thermal cationic polymerization initiators have the function of generating ions by heat. Regarding thermal cationic polymerization initiators, as cationic components, sulfonium cations, quaternary ammonium cations, iodonium cations, etc. can be listed. As anionic components, antimony hexafluoride anions, phosphorus hexafluoride anions, tetrakis(pentafluorophenyl)borate anions, trifluoromethanesulfonic acid, etc. can be listed.

[0193] The thermal radical polymerization initiator has a function of generating radicals by heat. Examples of the thermal radical polymerization initiator include azo thermal polymerization initiators and organic peroxide polymerization initiators.

[0194] Examples of the organic peroxide polymerization initiator include dialkyl peroxides such as diacetyl peroxide, di-tert-butyl peroxide, di-tert-hexyl peroxide, diisopropyl peroxide, tert-butylisopropyl peroxide, α,α′-bis(tert-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexyne-3,2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,3-bis(tert-butylperoxyisopropyl)hexane, and (2-ethylhexanoyl)(tert-butyl)peroxide;

[0195] Dipropionyl peroxide, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, bis(3,5,5-trimethylhexanoyl)peroxide, 1,1,3,3-tetramethylbutyl peroxyneodecanoate, α-isopropylphenyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneoheptanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate Peroxyesters such as tert-butyl peroxyisobutyrate, di-tert-butyl peroxyhexahydroterephthalate, 1,1,3,3-tetramethylbutyl peroxy-3,5,5-trimethylhexanoate, tert-amyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, dibutyl peroxytrimethyladipate, 2,5-dimethyl-2,5-di-ethylhexanoyl peroxyhexane, tert-hexyl peroxy-2-ethylhexanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-butyl peroxylaurate, tert-butyl peroxyisopropyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate;

[0196] Ketone peroxides such as methyl ethyl ketone peroxide, methyl isobutyl ketone peroxide, acetylacetone peroxide, cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, methylcyclohexanone peroxide, tert-butyl benzoate, and pivaloyl tert-butyl peroxide;

[0197] Peroxy ketals such as 2,2-bis(tert-butylperoxy)butane, 2,2-bis(4,4-di-tert-butylperoxycyclohexyl)propane, 1,1-bis(tert-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-hexylperoxy)cyclohexane, 4,4-bis(tert-butylperoxy)butyl valerate; hydroperoxides such as tert-butyl hydroperoxide, cumene hydroperoxide, diisopropylbenzene hydroperoxide, 2,5-dimethylcyclohexane-2,5-dihydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, and p-menthane hydroperoxide;

[0198] Diacyl peroxides such as dibenzoyl peroxide, didecanoyl peroxide, dilauroyl peroxide, diisobutyryl peroxide, bis-3,5,5-trimethylhexanol peroxide, m-toluoylbenzoyl peroxide, succinic acid peroxide, 2,4-dichlorobenzoyl peroxide;

[0199] Peroxydicarbonates such as bis(tert-butylcyclohexyl)peroxydicarbonate, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, tert-butylperoxyisopropyl carbonate, di-2-ethylhexyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, di-3-methoxybutyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, tert-amylperoxyisopropyl carbonate, tert-butylperoxy-2-ethylhexyl carbonate, and 6-bis(tert-butylperoxycarboxyoxy)hexane are not limited thereto.

[0200] From the viewpoint of storage stability, dialkyl peroxides are preferred, and di-tert-butyl peroxide is more preferred.

[0201] Examples of the azo thermal polymerization initiator include 2,2'-azobisisobutyronitrile and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile);

[0202] 1,1'-azobis(cyclohexane-1-carbonitrile) and other 1,1'-azobis-1-alkanenitrile 2,2'-azobis(2-hydroxymethylpropionitrile), 2,2'-azobis(2-hydroxymethylpropionitrile) and other 2,2'-azobispropiononitrile; 2,2'-azobis(N-butyl-2-methylpropionamide), 2,2'-azobis(N-cyclohexyl-2-methylpropionamide) and other 2,2'-azobispropionamide;

[0203] As well as dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-(2-imidazolin-2-yl)propane], 1-[(1-cyano-1-methylethyl)azo]formamide, etc.

[0204] Examples of the azo compound having a carboxyl group or a hydroxyl group include, but are not limited to, 4,4'-azobis(4-cyanovaleric acid), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-methyl-N-(2-hydroxyethyl)propionamide), and 2,2'-azobis(N-(carboxyethyl)-2-methylpropionamidine) tetrahydrate.

[0205] From the viewpoint of storage stability, 2,2'-azobispropionamides are preferred, and 2,2'-azobis(N-butyl-2-methylpropionamide) is more preferred.

[0206] The 10-hour half-life temperature of the thermal radical polymerization initiator is preferably 60° C. to 200° C., more preferably 80° C. to 180° C., further preferably 100° C. to 150° C., and particularly preferably 105° C. to 130° C. By setting the temperature to 60° C. or higher, the storage stability of the resin composition layer can be improved, and by setting the temperature to 200° C. or lower, the heat aging step of the sealant layer can be shortened.

[0207] The 10-hour half-life temperature is the temperature at which the thermal polymerization initiator is reduced to half of the initial value by thermal decomposition after 10 hours. Specifically, for the free radicals of the thermal polymerization initiator, a thermal polymerization initiator solution is prepared using an inert solvent and sealed in a glass tube after nitrogen substitution. It is immersed in a constant temperature layer set to a specified temperature for 10 hours and thermally decomposed, and the amount of the remaining thermal polymerization initiator is measured. By performing these series of operations at several temperatures, the half-life can be calculated based on the straight line obtained by drawing.

[0208] Based on the total amount (100% by mass) of the resin composition layer, the content of the thermal radical polymerization initiator (the total content when two or more are used in combination) is preferably 0.01% by mass to 20% by mass, more preferably 0.05% by mass to 10% by mass, and further preferably 0.1% by mass to 5% by mass. By setting the content to the above, the adhesion can be appropriately adjusted.

[0209] [monomer]

[0210] In the present embodiment, the monomer refers to a compound having a radical polymerizable group which is added to the resin composition and which is the minimum structural unit constituting an oligomer or a polymer.

[0211] As free radical polymerizable groups, for example, (meth)acryloyl, N-vinyl, vinyl ether, allyl, unsaturated carboxylic acid groups, etc. can be listed. In addition, the monomer can be a monofunctional monomer or a polyfunctional monomer. In addition, "monofunctional" in this specification refers to a compound having only one polymerizable group in one molecule, and "difunctional" and "trifunctional" refer to compounds having two and three polymerizable groups in one molecule, respectively. In addition, in this specification, difunctional and above are collectively referred to as "polyfunctional".

[0212] Specific examples of the monomer include: 2-methoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, dipropylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-(2-ethoxyethoxy)ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylhexylethylene oxide (ethylene oxide) ester, 2-ethylhexyl (meth)acrylate ... oxide, EO) modified (meth) acrylate, 2-hydroxyethyl (meth) acrylate, 2-hydroxypropyl (meth) acrylate, 4-hydroxybutyl (meth) acrylate, β-carboxyethyl (meth) acrylate, monohydroxyethyl phthalate (meth) acrylate, 4-tert-butyl cyclohexanol (meth) acrylate, tetrahydrofurfuryl acrylate, alkoxylated tetrahydrofurfuryl acrylate, caprolactone (meth) acrylate, isononyl (meth) acrylate, n-octyl (meth) acrylate, isooctyl (meth) acrylate, lauryl (meth) acrylate, stearyl (meth) acrylate, isopentyl (meth) acrylate, 2-phenoxyethyl (meth) acrylate, propyl (meth) acrylate Isodecyl (meth)acrylate, tridecyl (meth)acrylate, 3,3,5-trimethylcyclohexanol (meth)acrylate, cyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, tert-butylcyclohexyl (meth)acrylate, isobornyl (meth)acrylate, norbornyl (meth)acrylate, dicyclopentyl (meth)acrylate, dicyclopentenyl (oxyethyl) (meth)acrylate, 1,4-cyclohexanedimethanol (meth)acrylate, cyclic trimethylolpropane formaldehyde (meth)acrylate, benzyl (meth)acrylate, phenol EO modified (meth)acrylate, EO modified (2) nonylphenol acrylate, propylene oxide (propylene oxide) oxide, PO) modified nonylphenol acrylate, phenoxyethyl (meth) acrylate, phenoxypolyethylene glycol (meth) acrylate, 2-hydroxy-3-phenoxypropyl (meth) acrylate, 2-methyl-2-ethyl-1,3-dioxolan-4-yl) methyl acrylate, hydroxyethyl acrylamide, dimethylaminopropyl acrylamide, N-acryloyloxyethyl hexahydrophthalimide, acryloyl morpholine, 3-((meth)acryloyloxy)propyl trimethoxysilane a monofunctional (meth)acrylate monomer having one (meth)acryloyl group in the molecule, such as 1,4-dimethyl-1,4-dioxane, 3-((meth)acryloyloxy)propyltriethoxysilane, 2-(meth)acryloyloxyethyl isocyanate, or a monofunctional vinyl monomer having one N-vinyl group in the molecule, such as N-vinylcarbazole, 1-vinylimidazole, N-vinyl-2-pyrrolidone, N-vinylcaprolactam, N-vinylformamide, N-vinyloxazolidinone, N-vinylmethyloxazolidinone,

[0213] 1,3-Butanediol di(meth)acrylate, 1,4-Butanediol di(meth)acrylate, 3-methyl-1,5-pentanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, 1,2-dodecanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, polyethylene glycol (200) di(meth)acrylate Acrylate, polyethylene glycol (300) di(meth)acrylate, polyethylene glycol (400) di(meth)acrylate, polyethylene glycol (600) di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, EO modified (2) 1,6-hexanediol di(meth)acrylate, PO modified 1,6-hexanediol di(meth)acrylate, E difunctional (meth)acrylate monomers having two (meth)acryloyl groups in the molecule such as O-modified neopentyl glycol di(meth)acrylate, PO-modified (2) neopentyl glycol di(meth)acrylate, (neopentyl glycol-modified) trimethylolpropane di(meth)acrylate, trimethylol acid EO-modified diacrylate, tricyclodecane di(meth)acrylate, dimethylol tricyclodecane di(meth)acrylate, bisphenol A di(meth)acrylate, EO-modified (4) bisphenol A di(meth)acrylate, PO-modified (4) bisphenol A di(meth)acrylate, EO-PO-modified bisphenol A di(meth)acrylate, bisphenol F di(meth)acrylate, EO-modified bisphenol F di(meth)acrylate, PO-modified bisphenol F di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, ethoxylated cyclohexanemethanol di(meth)acrylate, and dicyclopentane di(meth)acrylate,

[0214] a difunctional (meth)acrylate monomer having one (meth)acryloyl group and one allyl group in the molecule, such as 2-(allyloxymethyl)methacrylate and 2-(allyloxymethyl)ethylacrylate,

[0215] trimethylolpropane tri(meth)acrylate, EO modified (3) trimethylolpropane tri(meth)acrylate, EO modified (6) trimethylolpropane tri(meth)acrylate, PO modified (3) trimethylolpropane tri(meth)acrylate, ε-caprolactone modified tri-(2-acryloyloxyethyl) isocyanurate, ethoxylated isocyanuric acid tri(meth)acrylate, tris(2-hydroxyethyl) isocyanurate tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, tri-(2-acryloyloxyethyl) isocyanurate, ethoxylated isocyanuric acid tri(meth)acrylate, tri- ... tri-(2-acryloyloxyethyl) isocyanurate tri(meth)acrylate, tri-(2-acryloyloxyethyl) isocyanurate tri(meth)acrylate, tri-(2-acryloyloxyethyl) isocyanurate tri(meth)acrylate, tri-(2-acryloyloxyethyl) isocyanurate tri(meth)acrylate, tri-(2-acryloyloxyethyl) isocyanurate tri(meth)acrylate, tri-(2-ac trifunctional (meth)acrylate monomers having three (meth)acryloyl groups in the molecule, such as methylolpropane tri((meth)acryloyloxypropyl) ether, isocyanuric acid alkylene oxide-modified tri(meth)acrylate, propionate dipentaerythritol tri(meth)acrylate, tri((meth)acryloyloxyethyl)isocyanurate, hydroxypivalaldehyde-modified dimethylolpropane tri(meth)acrylate, sorbitol tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, EO-modified glycerol tri(meth)acrylate, PO-modified glycerol tri(meth)acrylate,

[0216] Tetrafunctional (meth)acrylate monomers having four acryloyl groups in the molecule such as pentaerythritol tetra(meth)acrylate, EO-modified (4) pentaerythritol tetra(meth)acrylate, di-trimethylolpropane tetra(meth)acrylate, sorbitol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate propionate, tetramethylolmethane tetra(meth)acrylate, pentafunctional (meth)acrylate monomers having five (meth)acryloyl groups in the molecule such as dipentaerythritol penta(meth)acrylate, sorbitol penta(meth)acrylate, hexafunctional (meth)acrylate monomers having six (meth)acryloyl groups in the molecule such as dipentaerythritol hexa(meth)acrylate, sorbitol hexa(meth)acrylate, phosphazene alkylene oxide-modified hexa(meth)acrylate, ε-caprolactone-modified dipentaerythritol hexa(meth)acrylate, etc. are not limited thereto.

[0217] In addition, the above-mentioned "EO" means "ethylene oxide" and "PO" means "propylene oxide." The monomers may be used alone or in combination of two or more.

[0218] Among them, as the (meth)acrylate compound, from the viewpoint of embedding properties, a difunctional to hexafunctional (meth)acrylate monomer is preferred, and a difunctional to trifunctional (meth)acrylate monomer is more preferred. Specifically, 1,6-hexanediol di(meth)acrylate, EO-modified (4) bisphenol A di(meth)acrylate, and EO-modified (3) trimethylolpropane tri(meth)acrylate are preferred.

[0219] Based on the total amount (100% by mass) of the resin composition layer, the content of the monomer (the total content when two or more monomers are used in combination) is preferably 0.01% by mass to 30% by mass, more preferably 0.05% by mass to 20% by mass, and further preferably 0.1% by mass to 15% by mass. By setting the content to the above, the embedding property can be appropriately adjusted.

[0220] [Oligomer]

[0221] In the present embodiment, the oligomer is a polymer having structural units based on 2 to 100 monomers containing a radical polymerizable group, and has a weight average molecular weight of 400 to 9,999. The weight average molecular weight of the oligomer is more preferably 400 to 5,000, and even more preferably 500 to 3,000.

[0222] Examples of the polymerizable groups possessed by the oligomer include (meth)acryloyl, N-vinyl, vinyl ether, allyl, and unsaturated carboxylic acid groups, preferably (meth)acryloyl. In addition, the radical polymerizable oligomer may be monofunctional or polyfunctional. The number of polymerizable groups is preferably 1 to 6 per molecule, more preferably 2 to 4.

[0223] Specific examples of the oligomer include urethane acrylate oligomers such as aliphatic urethane acrylate oligomers and aromatic urethane acrylate oligomers, acrylate oligomers, polyester acrylate oligomers, and epoxy acrylate oligomers. The oligomers may be used alone or in combination of two or more.

[0224] From the viewpoint of embedding properties, the (meth)acrylate compound of the present disclosure preferably includes an alkylene oxide-modified (meth)acrylate compound having two or more (meth)acryloyl groups in the molecule.

[0225] Based on the total amount (100% by mass) of the resin composition layer, the content of the oligomer (the total content when two or more are used in combination) is preferably 0.01% by mass to 30% by mass, more preferably 0.05% by mass to 20% by mass, and further preferably 0.1% by mass to 15% by mass. By setting the content to the above, the embedding property can be appropriately adjusted.

[0226] [Other ingredients]

[0227] The resin composition layer of the present disclosure may also contain other components within the scope that does not impair the purpose of the present disclosure. For example, a colorant, a dispersant, a surface adjustment additive, a softener, an antistatic agent, a lubricant, an anti-blocking agent, an adhesion improver, etc. may be added. From the perspective of controlling the film properties such as the viscoelasticity of the resin composition layer, it is preferred to contain a colorant, a surface adjustment additive, and an adhesion improver.

[0228] Examples of colorants include black pigments, black dyes, and pigments of red, green, blue, yellow, purple, cyan, and magenta. Toning can also be performed by mixing a plurality of colorants. From the perspective of controlling film properties, the black pigment is preferably carbon black.

[0229] When the colorant is a pigment, the number average primary particle diameter is preferably 10 nm to 100 nm. By setting it to the above range, it is easy to maintain the viscosity of the resin composition at a level suitable for coating. In addition, the number average primary particle diameter of the pigment can be obtained by the same method as the metal oxide particles (B).

[0230] From the viewpoint of embedding properties, the content of the colorant (the total content when two or more types are included) is preferably 0.1 to 30% by mass, more preferably 0.5 to 25% by mass, based on the total amount (100% by mass) of the resin composition layer.

[0231] Examples of the surface conditioning additive include surfactants having a weight average molecular weight (Mw) of 1,000 to 9,999, such as silicone, silicone acrylic, fluorine, and ethylene glycol surfactants, which do not contain a radical polymerizable group. Among them, silicone and silicone acrylic surfactants are particularly preferred from the viewpoint of adhesion.

[0232] As a silicon-based surface adjustment additive, for example, a modified polysiloxane compound obtained by introducing an organic group into a part of the methyl group of polydimethylsiloxane is preferred. Examples of modification include polyether modification, methylstyrene modification, alcohol modification, alkyl modification, aralkyl modification, fatty acid ester modification, epoxy modification, amine modification, amino modification, mercapto modification, etc., but are not particularly limited to these. These modification methods can be used in combination. Among them, in terms of compatibility, etc., polyether-modified polysiloxane compounds and aralkyl-modified polysiloxane compounds are preferred.

[0233] From the viewpoint of coating suitability, the content of the surface conditioning additive is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, based on the total amount (100% by mass) of the resin composition layer.

[0234] As the adhesion improver, oligomers having a weight average molecular weight (Mw) of 1,000 to 9,999 and not containing a radical polymerizable group can be cited. Examples include rosin resins, terpene resins, alicyclic petroleum resins, and aromatic petroleum resins. The weight average molecular weight (Mw) of the adhesion improver is more preferably 2,000 to 8,000, and further preferably 3,000 to 5,000.

[0235] From the viewpoint of adhesion, the content of the adhesion improver is preferably 0.1% by mass to 20% by mass, and more preferably 1% by mass to 15% by mass, based on the total amount (100% by mass) of the resin composition layer.

[0236] Example

[0237] Hereinafter, the present disclosure will be specifically described by way of Examples and Comparative Examples, but the present disclosure is not particularly limited to the Examples. In the following description, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.

[0238] The numerical values ​​obtained in the present examples are values ​​obtained by the following method.

[0239] [Glass transition temperature (Tg) of resin (A)]

[0240] The coating liquid of resin (A) was applied to the release layer of a protective film (manufactured by Mitsui Chemicals Tohcello, SP-PET-O3) having a thickness of 75 μm so that the thickness after drying was 20 μm. After drying in a hot air oven at 100°C for 3 minutes, the release layer side of a release liner (manufactured by Mitsui Chemicals Tohcello, SP-PET-O1) having a thickness of 50 μm was attached to the resin (A) side. Then, the protective film and the release liner were peeled off, and the Tg of the obtained resin (A) was measured using a differential scanning calorimeter (manufactured by TA Instruments, "Discovery DSC 2500"). About 2 mg of the sample was placed in an aluminum pan, weighed, and placed in a differential scanning calorimeter. Using an aluminum pan of the same type without the sample as a reference, the pan was kept at 100°C for 5 minutes and then rapidly cooled to -50°C using liquid nitrogen. Thereafter, the temperature was increased at a rate of 5°C / min, and the glass transition temperature (Tg) of the resin (A) was determined based on the obtained differential scanning calorimetry (DSC) chart.

[0241] [Weight average molecular weight (Mw) and number average molecular weight (Mn)]

[0242] The weight average molecular weight (Mw) and the number average molecular weight (Mn) were determined by using a GPC "LC-GPC system" manufactured by Shimadzu Corporation and converting polystyrene with a known molecular weight as a standard substance.

[0243] Device name: LC-GPC system "Prominence" manufactured by Shimadzu Corporation

[0244] Pipe string: Four GMHXL pipes manufactured by Tosoh and one HXL-H pipe manufactured by Tosoh were connected.

[0245] Mobile phase solvent: tetrahydrofuran

[0246] Flow rate: 1.0mL / min

[0247] Column temperature: 40℃

[0248] [Solid content]

[0249] The mass of the aluminum cup is measured using a precision balance (W0). Then, about 1 g of the sample is placed in the aluminum cup, and the mass of the sample with the aluminum cup is measured using a precision balance (W1). After heating the sample with the aluminum cup in an oven at 150°C for 120 minutes, it is taken out of the oven and returned to room temperature. The residual mass (W2) of the heated sample with the aluminum cup is measured using a precision balance. Then, the solid content is calculated using the formula (W2-W0) / (W1-W0)×100(%).

[0250] [Acid value]

[0251] The "acid value" means the acid value per 1 g of the solid content of the resin (A), and is determined by a potentiometric titration method in accordance with JIS K 0070.

[0252] [Production Example of Resin (A)]

[0253] [Production Example of (meth)acrylic resin (a) (R-1)]

[0254] In a reaction container (hereinafter referred to as "reaction container") including a stirrer, a thermometer, a reflux cooling tube, a dripping device, and a nitrogen inlet tube, 80 parts of ethyl acetate, 20 parts of methyl methacrylate, 79 parts of n-butyl methacrylate, 1 part of methacrylic acid, and 0.1 parts of 2,2'-azobisisobutyronitrile as an initiator were placed, and the environment in the reaction container was replaced with nitrogen gas. Thereafter, the reaction was started while being heated to 65°C under a nitrogen environment while being stirred. Thereafter, the reaction solution was reacted at 65°C for 4 hours. After the reaction was completed, it was cooled and diluted with ethyl acetate to obtain a solution of acrylic resin (R-1) with a weight average molecular weight (Mw): 35,000, a dispersion (Mw / Mn): 2, a glass transition temperature (Tg): 35°C, an acid value: 7 mgKOH / g, and a solid content: 25%.

[0255] [Production Example of (meth)acrylic resin (a) (R-2 to R-4)]

[0256] (Meth)acrylic resins (a) (R-2 to R-4) were prepared by the same method as that for (meth)acrylic resin (a) (R-1) except that the composition and blending amount (parts by mass) were changed to those shown in Table 1. In addition, blank columns indicate that no blending was performed, and the solid content was 25%.

[0257] [Table 1]

[0258] [Table 1]

[0259]

[0260] The abbreviations in the table are as follows.

[0261] BA: n-butyl acrylate

[0262] MMA: Methyl Methacrylate

[0263] nBMA: n-butyl methacrylate

[0264] MAA: Methacrylic acid

[0265] 2HEMA: 2-Hydroxyethyl Methacrylate

[0266] GMA: Glycidyl Methacrylate

[0267] MOI: 2-methacryloyloxyethyl isocyanate

[0268] [Production Example of Urethane Resin (R-5)]

[0269] In a glass flask including a stirrer, a thermometer, a reflux cooler, a nitrogen inlet pipe, and a decompression device, 166 parts of terephthalic acid, 146 parts of adipic acid, 212 parts of 3-methyl-1,5-pentanediol, and 25 parts of ethylene glycol were placed, and nitrogen was introduced while stirring, and the temperature was slowly raised at normal pressure, and the reaction was performed at 200°C to 230°C for about 8 hours to obtain a liquid with an acid value of 43 mgKOH / g. Then, 0.01 parts of tetra-n-butoxytitanium was added, and after nitrogen substitution, it was stirred at 180°C for 30 minutes in a sealed state. Then, the reaction was performed at 230°C and 5 mmHg for 2 hours to obtain a polyester diol with an acid value of 1.1 mgKOH / g, a hydroxyl value of 114.2 mgKOH / g, a weight average molecular weight (Mw): 982, and a hue of 10 (American Public Health Association (APHA) method, the same below).

[0270] Next, 734 parts of the polyester diol, 23.9 parts of dimethylol propionic acid, 219 parts of toluene diisocyanate, and 242 parts of toluene were placed in a reaction vessel including a stirrer, a thermometer, a reflux cooler, a dropping device, and a nitrogen inlet pipe, and reacted at 50° C. for 8 hours under a nitrogen atmosphere. 1200 parts of toluene was added thereto to obtain a solution of a urethane prepolymer having an isocyanate group at the end.

[0271] Next, the obtained prepolymer solution was heated to 70°C, and while maintaining the temperature, a solution obtained by mixing 20.0 parts of 1,3-diaminopropane, 3.1 parts of benzylamine, 600 parts of 2-propanol, and 961 parts of toluene was added dropwise over 1 hour. After the addition was completed, the mixture was further reacted at 70°C for 6 hours, thereby obtaining a solution of a urethane resin (R-5) having a weight average molecular weight (Mw): 150,000, a dispersion degree (Mw / Mn): 4.5, a glass transition temperature (Tg): 18°C, an acid value: 10 mgKOH / g, and a solid content: 25%.

[0272] [Production Example of Dispersion of Metal Oxide Particles (B)]

[0273] [Preparation Example of Dispersant]

[0274] In a four-necked flask equipped with a stirrer, a reflux cooling tube, a gas introduction tube, and a thermometer, 60.0 parts of isomyristyl alcohol, 127.8 parts of ε-caprolactone, 112.2 parts of δ-valerolactone, and 0.1 parts of monobutyltin (IV) oxide as a catalyst were placed, replaced with nitrogen gas, and stirred at 120° C. for 3 hours and reacted. After confirming that 98% of the reaction was completed by solid content measurement, 30.5 parts of pyromellitic dianhydride were added and reacted at 100° C. for 5 hours. After the reaction was completed, the mixture was cooled, and the solid content was adjusted with methyl ethyl ketone to obtain a linear acidic dispersant with a solid content of 81% and an acid value of 49 mgKOH / g.

[0275] [Production Example of Dispersion (D-1) of Metal Oxide Particles (B)]

[0276] The ZrO 2 (PCS60, manufactured by Nippon Electric Industries, Ltd., number average primary particle diameter 20 nm, specific surface area as determined by the BET method 50 m 2 / g~70m 2 / g), 724 parts of the above-mentioned dispersant, 80.2 parts of the above-mentioned dispersant, and 1195.8 parts of methyl ethyl ketone were mixed, and after preliminary dispersion using a disperser, a dyno-mill with a volume of 0.6 L filled with 1800 g of zirconia beads with a diameter of 0.3 mm was used for formal dispersion for 2 hours. After the dispersion was completed, the zirconia beads were removed to obtain a dispersion (D-1) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2%.

[0277] [Production Example of Dispersion (D-2) of Metal Oxide Particles (B)]

[0278] The metal oxide particles (B) were replaced with TiO 2 (MT-05, manufactured by Tayca, number average primary particle diameter 10 nm, specific surface area as determined by the BET method 20 m 2 / g~50m 2 / g), and the dispersant was changed to DISPERBYK (registered trademark)-180 (manufactured by BYK-Chemie, solid content 81%). In addition, a dispersion (D-2) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2% was prepared by the same method as the preparation of the dispersion (D-1) of metal oxide particles (B).

[0279] [Production Example of Dispersion (D-3) of Metal Oxide Particles (B)]

[0280] The metal oxide particles (B) were replaced with SiO 2 (AEROSIL (registered trademark) 50, manufactured by Japan Aerosil Co., Ltd., number average primary particle diameter 50nm, specific surface area obtained by BET method 35m 2 / g~65m 2 / g), and except for this, a dispersion (D-3) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2% was produced by the same method as that for producing the dispersion (D-1) of metal oxide particles (B).

[0281] [Production Example of Dispersion (D-4) of Metal Oxide Particles (B)]

[0282] The metal oxide particles (B) were changed to Al 2 O 3(AEROXIDE (registered trademark) Alu C, manufactured by Japan Aerosil Co., Ltd., number average primary particle diameter 13nm, specific surface area obtained by BET method 85m 2 / g~115m 2 / g), and except for this, a dispersion (D-4) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2% was produced by the same method as that for producing the dispersion (D-1) of metal oxide particles (B).

[0283] [Production Example of Dispersion (D-5) of Metal Oxide Particles (B)]

[0284] The metal oxide particles (B) were replaced with TiO 2 (MT-700B, manufactured by Tayca, number average primary particle diameter 80 nm, specific surface area as determined by the BET method 20 m 2 / g~60m 2 / g), and except for this, a dispersion (D-5) of metal oxide particles (B) having a solid content of 39.4% and a concentration of metal oxide particles (B) of 36.2% was produced by the same method as that for producing the dispersion (D-1) of metal oxide particles (B).

[0285] [Example 1] [Manufacturing of resin composition]

[0286] The solution of the (meth)acrylic resin (a) (R-1) as the resin (A): 314.8 parts (resin (A) 78.7 parts, solvent 236.1 parts), the dispersion of metal oxide particles (B): 41.4 parts (solid content 16.3 parts (of which metal oxide particles (B) 15 parts), solvent 25.1 parts), the epoxy crosslinking agent jER (registered trademark) YX8034 (manufactured by Mitsubishi Chemical Corporation): 5 parts as a crosslinking agent as other components, and methyl ethyl ketone: 55 parts as a solvent were sequentially added while stirring with a disperser, and stirred until sufficiently uniform. Subsequently, the mixture was filtered with a membrane filter having a pore size of 10 μm to remove coarse foreign matter that caused uneven coating, and a resin composition having a solid content of 24% was obtained.

[0287] In addition, the resin (A), metal oxide particles (B), crosslinking agent, and other components described in Table 2 are expressed in terms of solid content.

[0288] [Manufacturing of sealing sheet]

[0289] The resin composition was applied to the release layer of a protective film (SP-PET-O3 manufactured by Mitsui Chemicals Tohcello Co., Ltd.; Sq of the release layer side was 0.3 μm) having a thickness of 38 μm so that the thickness after drying was 20 μm, and dried in a hot air oven at 100° C. for 3 minutes to form a resin composition layer. Subsequently, the release layer side of a release liner (SP-PET-O1 manufactured by Mitsui Chemicals Tohcello Co., Ltd.) having a thickness of 50 μm was attached to the exposed resin composition layer, and aged at 0° C. for 7 days to obtain a sealing sheet of Example 1 in which the protective film / resin composition layer having a thickness of 20 μm / release liner were laminated in this order.

[0290] [Thickness Tt of Sealing Sheet, Thickness Ta of Resin Composition Layer, Thickness Tb of Protective Film, Thickness Tc of Release Liner]

[0291] Determine 10 equally spaced locations within the range from the end in the width direction to the other end of a sealing sheet cut into a size of 10 cm × 10 cm, measure the thickness at the 10 locations, and set the average value thereof as the thickness Tt of the sealing sheet. Then, peel off the release liner from the sealing sheet, and measure the thickness of the release liner after peeling at 10 locations corresponding to the same position as the position. Set its average value as Tc. Thereafter, further peel off the protective film from the resin composition layer, and measure the thickness of the protective film after peeling at 10 locations corresponding to the same position as the position. Set its average value as Tb. The thickness Ta of the resin composition layer is obtained by the following (Formula 2). In addition, the thickness is measured using MH-15M (manufactured by Nikon).

[0292] Ta=Tt-Tc-Tb (Formula 2)

[0293] [Tan δ peak intensity and tan δ40 of resin composition layer]

[0294] Except that the thickness of the resin composition layer is changed to 50 μm, the sealing sheet is prepared in the same manner as in the manufacturing example of the sealing sheet. Cut into 0.5 cm × 2 cm size, and peel off the protective film and the release liner. For the obtained resin composition layer, the dynamic viscoelasticity measuring device DVA-200 / L2 (manufactured by IT Measurement and Control Co., Ltd.) is used to measure the dynamic viscoelasticity and plot the loss tangent (tan δ) at a frequency of 10 Hz, a measurement temperature range of -50°C to 150°C, a heating rate of 5°C / min, and a tensile mode. The peak intensity (tan δ peak intensity) of the loss tangent (tan δ) and the loss tangent (tan δ40) at 40°C are read from the obtained curve graph.

[0295] [Refractive index]

[0296] The sealing sheet of Example 1 was cut into a size of 2 cm×5 cm, and the protective film and the release liner were peeled off. The refractive index of the obtained resin composition layer was measured using an Abbe refractometer (DR-M2, Atago Co., Ltd.).

[0297] [Haze, total light transmittance]

[0298] The sealing sheet of Example 1 was cut into a size of 2.5 cm × 10 cm, and a glass plate (blue plate glass, manufactured by Kawamura Kyuzo Shoten Co., Ltd.) with a thickness of 1.1 mm was attached to the surface after peeling off the release liner, and then the protective film was peeled off. The haze value and total light transmittance of the resin composition layer were measured using a haze meter (NDH8000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0299] [Chroma * ]

[0300] The sealing sheet of Example 1 was cut into a size of 2.5 cm × 10 cm, and a glass plate (blue plate glass, manufactured by Kawamura Kyuzo Shoten) with a thickness of 1.1 mm was attached to the surface after peeling off the release liner, and then allowed to stand at 180°C for 120 minutes. The glass plates were placed on a standard white plate in a manner of contact, and the protective film was peeled off to prepare a structure of a standard white plate / glass plate / resin composition layer. A colorimeter (X-Rite eXact, manufactured by X-Rite) was used, and the light source condition was set to D50 / 2°, and a was measured at any three locations on the resin composition layer. * Value and b * Use the following (Formula 1) to calculate the average value according to a * The average value of b * The chroma C is calculated by averaging the values. * .

[0301] C * =(a *2 +b *2 ) 0.5 (Formula 1)

[0302] [Root mean square height Sq]

[0303] The peeling surface of the protective film cut into a size of 10 cm×10 cm was measured at 5 random locations using a confocal microscope (Lasertec, OPTELICS HYBRID+, objective lens 20 times) in accordance with ISO 25178, and then analyzed and calculated using data analysis software (LMeye8).

[0304] [Evaluation methods and criteria]

[0305] [Embeddability]

[0306] A test substrate imitating the concavoconvexity of a micro-LED substrate was prepared (a plate with a concave portion with a width of 200 μm, a convex portion with a height of 5 μm, and a convex portion with a width of 200 μm formed on one side of a 25 mm×25 mm glass plate). A schematic cross-sectional diagram of the test substrate is shown in FIG. Figure 3 middle.

[0307] The sealing sheet is cut into a size of 30 mm × 30 mm, the release liner is peeled off to expose the resin composition layer, and the resin composition layer is placed on the surface of the test substrate with a concave-convex portion. Thereafter, TPX (Opulent X-44B, manufactured by Mitsui Chemicals Tohcello) with a thickness of 50 μm and a vinyl chloride film (SEREBU T, manufactured by Okamoto) with a thickness of 2.0 mm as a buffer material are sequentially stacked on the protective film, and then cardboard is stacked to prevent sticking. The laminate comprising a glass substrate / resin composition layer / protective film / buffer material (TPX / vinyl chloride film) / cardboard is pressed from above to the substrate surface under the conditions of 5 MPa and 100 ° C for 20 minutes, so that the resin composition layer is filled into the concave portion of the test substrate, thereby forming a sealing layer. After pressing, the buffer material and the cardboard are peeled off.

[0308] The sealing layer extending from the obtained test substrate with a sealing layer to the side was roughly removed using a cutter, and then filed to remove the sealing layer remaining on the side of the test substrate with a sealing layer, exposing the side of the test substrate, thereby making it possible to observe the concave and convex parts. The embedding property was evaluated by observing the concave parts of the test substrate at any 15 locations using a microscope. The groove was considered to be embedded when the maximum gap between the sealing layer and the test substrate in the concave part of the test substrate was less than 1 μm.

[0309] The evaluation criteria are as follows, with A to C being considered good, and D being considered an evaluation that did not achieve the target performance.

[0310] A: There are 14 or more buried grooves.

[0311] B: The number of buried grooves is 13 or less and 11 or more.

[0312] C: The number of buried grooves is 10 or less and 8 or more.

[0313] D: The number of buried grooves is 7 or less.

[0314] [Seamlessness]

[0315] Prepare a sealing sheet obtained by cutting the sealing sheet of Example 1 into 25mm×100mm, peel off the release liner to expose the resin composition layer, and place it on a glass plate (25mm×100mm×1.1mm, blue plate glass, manufactured by Kawamura Jiuzhang Shoten Co., Ltd.) in a manner that the ends are matched. Thereafter, TPX (Opulent X-44B, manufactured by Mitsui Chemicals Tohcello) with a thickness of 50μm and a vinyl chloride film (SEREBU T, manufactured by Okamoto) with a thickness of 2.0mm as a buffer material are sequentially laminated on the protective film, and then cardboard is laminated to prevent sticking. The laminate comprising a glass plate / resin composition layer / protective film / buffer material (TPX / vinyl chloride film) / cardboard is pressed from above to the substrate surface under the conditions of 5MPa and 100°C for 20 minutes, and the glass plate and the resin composition layer are pressed to form a sealing layer on the glass plate. After pressing, the cushion material and the cardboard were peeled off to prepare a seamless test piece. The protective film was peeled off from the obtained seamless test piece, and the haze (Hs) was measured.

[0316] Next, prepare two sealing sheets obtained by cutting the sealing sheets into a size of 25 mm in length and 50 mm in width, peel off the release film to expose the resin composition layer, and place them on a glass plate (25 mm × 100 mm × 1.1 mm, blue plate glass, manufactured by Kawamura Hisazo Shoten Co., Ltd.) in a horizontal arrangement with the ends aligned. Thereafter, press in the same manner as the seamless test piece to obtain a joint test piece in which the interface between the sealing layers formed by the two sealing sheets is used as a joint. Peel off the protective film from the joint test piece, and measure the haze (Hj) of the joint portion. Calculate the change in the haze (Hs) of the seamless test piece and the haze (Hj) of the joint test piece (|Hs-Hj| / 100(%)) and evaluate.

[0317] The evaluation criteria are as follows, with A to C being considered good, and D being considered an evaluation that did not achieve the target performance.

[0318] A: The amount of change is 0.5% or less.

[0319] B: The amount of change is more than 0.5% and less than 0.8%.

[0320] C: The amount of change is more than 0.8% and less than 1.0%.

[0321] D: The change is greater than 1.0%.

[0322] [Tightness]

[0323] A seamless test piece used for seamless evaluation was prepared, and the protective film was peeled off. The test piece including the glass plate and the sealing layer was left to stand at 180° C. for 120 minutes to prepare a test piece in which the glass plate and the sealing layer were in close contact with each other.

[0324] According to JIS K 5600-5-6 (cross-cut method), a 1 mm square right-angle grid pattern (25 grids) was made on the sealing layer of the test piece using a cross-cut guide and a cutter, and an adhesive tape (CT1835, manufactured by Nichiban) was attached to the grid-cut portion to closely adhere to the sealing layer. Within 5 minutes of attachment, the adhesive tape was peeled off at an angle of nearly 60° for 0.5 to 1.0 seconds. The peeled sealing layer was observed to evaluate the adhesion.

[0325] The evaluation criteria are as follows, with A to C being considered good, and D being considered an evaluation that did not achieve the target performance.

[0326] A: The number of completely peeled cells is 0, and there is only no partial peeling at the edge of the cut.

[0327] B: The number of completely peeled cells is 0, and there is only partial peeling at the edge of the cut.

[0328] C: The number of peeled cells is 1 or more and 2 or less.

[0329] D: The number of peeled cells is 3 or more.

[0330] [Visibility]

[0331] Prepare a seamless test piece used in the seamlessness evaluation, peel off the protective film, and let the test piece containing the glass plate and the sealing layer stand for 120 minutes at 180°C to make a test piece in which the glass plate is in close contact with the sealing layer. The test piece is placed in such a way that the sealing layer is in contact with the display surface of the LED display device (LED Name Badge (white), manufactured by Asco) to make a laminate comprising a display device / sealing layer / glass plate. Then, white text (capital letters A to C totaling 3 characters) is displayed on the display device with a black background. The observer observes the displayed text at two angles of 30° from the horizontal direction and 90° from the vertical direction. The observer visually compares and evaluates the deformation of the text displayed before and after the placement of the test piece and the blurring of the outline.

[0332] The evaluation criteria are as follows. A to B are considered good, and a value D is considered not to have achieved the target performance.

[0333] A: No distortion or blurring of the outline is observed at any angle.

[0334] B: Distortion and / or blurring of outlines are visible at any angle.

[0335] D: Distortion and / or blurring of outlines are visible at all angles.

[0336] [Examples 2 to 37], [Comparative Examples 1 to 10]

[0337] A sealing sheet was prepared and evaluated in the same manner as in Example 1 except that the content, thickness Ta and protective film were changed to those shown in Tables 2 to 5. In addition, any one of a crosslinking agent, an oligomer, a monomer, a polymerization initiator and other components was also added simultaneously.

[0338] In Tables 2 to 5, the amounts of resin (A), crosslinking agent, oligomer, monomer, polymerization initiator, and other components are expressed as solid content. The amount of metal oxide particles (B) expressed as solid content of dispersions (D-1 to D-5) is expressed in parentheses, and the amount of metal oxide particles (B) in dispersions (D-1 to D-5) is expressed in parentheses. Blank columns indicate that no mixing was performed.

[0339] The abbreviations in the table are as follows.

[0340] C-1: Epoxy crosslinking agent (jER (registered trademark) YX8034, hydrogenated bisphenol A type epoxy resin, manufactured by Mitsubishi Chemical Corporation)

[0341] C-2: isocyanate compound (Cosmonate (registered trademark) T100, 2,4-toluene diisocyanate, manufactured by Mitsui Chemicals Fine Co., Ltd.)

[0342] C-3: Silane coupling agent (KBE-403, 3-glycidyloxypropyltrimethoxysilane, manufactured by Shin-Etsu Silicones Co., Ltd.)

[0343] O-1: Urethane acrylate oligomer (KRM8667, manufactured by Daicel-Allnex, trifunctional, weight average molecular weight 2000, viscosity at 60°C 11,000 cps)

[0344] O-2: Epoxy acrylate oligomer (Miramer (registered trademark) HR6042, manufactured by MIWON, difunctional, weight average molecular weight 1400, viscosity at 25°C 21,000 cps)

[0345] O-3: Polyester acrylate oligomer (Miramer (registered trademark) PS4040, manufactured by MIWON, tetrafunctional, weight average molecular weight 1300, viscosity at 25°C 6,300 cps)

[0346] O-4: Acrylate oligomer (ART CURE (registered trademark) UN-9000PEP, manufactured by Negami Industries, difunctional, weight average molecular weight 5000, viscosity at 25°C 2,000,000 cps)

[0347] M-1: EO modified (3) trimethylolpropane triacrylate (Miramer (registered trademark) M3130, manufactured by MIWON, trifunctional, 25°C viscosity 65 cps)

[0348] M-2: 1,6-hexanediol diacrylate (Viscoat (registered trademark) #230, manufactured by Osaka Organic Chemical Industry Co., Ltd., difunctional, 25°C viscosity 7 cps)

[0349] I-1: di-tert-butyl peroxide (Perbutyl (registered trademark) D, manufactured by NOF Corporation)

[0350] I-2: 2,2'-azobis(N-butyl-2-methylpropionamide) (VAm-110, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0351] A-1: Phosphorus antioxidant (Adekastab PEP-36, manufactured by ADEKA)

[0352] A-2: Surface conditioning agent (BYK (registered trademark)-3440, manufactured by BYK-Chemie)

[0353] P-1: 38 μm thick protective film (SP-PET-O3, manufactured by Mitsui Chemicals Tohcello, Sq: 0.3 μm)

[0354] P-2: Protective film with a thickness of 75 μm (matt film (type M3), manufactured by IM Co., Ltd., Sq: 1.5 μm)

[0355] P-3: Protective film with a thickness of 50 μm (matt film (type M8), manufactured by IM, Sq: 1,0 μm)

[0356] P-4: Protective film with a thickness of 10 μm (matt film (type M3), manufactured by IM Co., Ltd., Sq: 1.5 μm)

[0357] P-5: Protective film with a thickness of 100 μm (matt film (type M8), manufactured by IM Co., Ltd., Sq: 1.0 μm)

[0358] P-6: Protective film with a thickness of 188 μm (matt film (type M3), manufactured by IM Co., Ltd., Sq: 1.5 μm)

[0359] P-7: 200 μm thick protective film (matt film (type M2), manufactured by IM, Sq: 2.0 μm)

[0360]

[0361]

[0362]

[0363]

[0364] In the present disclosure, it is known that in the case of a sealing sheet not containing metal oxide particles (B) having a number average primary particle diameter of 5 nm to 50 nm, there are problems in embedding property, adhesion, or visibility, as shown in Comparative Examples 1, 5, 6, and 10. In addition, in the case of a sealing sheet having a refractive index outside the range of 1.45 to 1.65, there are problems in seamlessness and visibility, as shown in Comparative Examples 2 to 4 and Comparative Examples 7 to 9.

[0365] The sealing sheets of Comparative Examples 1 to 10 could not satisfy embedding property and seamlessness at a high level in a well-balanced manner. In addition, they could not satisfy adhesion and visibility at a high level.

[0366] On the other hand, according to Examples 1 to 37, the encapsulating sheets of the present disclosure showed excellent embedding properties and excellent seamlessness as described in Tables 2 to 5. Furthermore, the adhesion and visibility were also excellent, and it was found that the encapsulating sheets of the present disclosure can be suitably used for encapsulating optical semiconductor elements.

[0367] This application claims priority based on Japanese Patent Application No. 2023-135317 filed on August 23, 2023, and priority based on Japanese Patent Application No. 2023-173435 filed on October 5, 2023, and all the contents disclosed in these are incorporated into this application.

[0368] Explanation of symbols

[0369] 1: Sealing sheet

[0370] 2: Resin composition layer

[0371] 2': Sealing layer

[0372] 3: Base material

[0373] 4: Release liner

[0374] 5: Optical semiconductor components

[0375] 6: Substrate

[0376] 7: Glass substrate

Claims

1. A sealing sheet for sealing an optical semiconductor element, characterized in that: The sealing sheet is sequentially provided with a protective film and a resin composition layer, The resin composition layer contains 5.3 to 48.2 parts by mass of metal oxide particles (B) based on 100 parts by mass of the total of the resin (A), the monomer, and the oligomer. The metal oxide particles (B) have a number average primary particle diameter of 5 nm to 50 nm, The refractive index of the resin composition layer is 1.45 to 1.

65.

2. The sealing sheet according to claim 1, characterized in that: The metal constituting the metal oxide particles (B) includes at least one selected from the group consisting of Ti, Al, and Zr.

3. The sealing sheet according to claim 1, characterized in that: The resin (A) includes at least one selected from the group consisting of (meth)acrylic resins (a) and urethane resins (b).

4. The sealing sheet according to claim 1, characterized in that: The resin composition layer has a haze of less than 12% and a total light transmittance of more than 80%. The resin composition layer is made of the International Commission on Illumination * a * b * The chroma C obtained from the color space * It ranges from 0 to 10.

5. The sealing sheet according to claim 1, characterized in that: The thickness Ta of the resin composition layer is 1 μm to 100 μm, The thickness Tb of the protective film is 10 μm to 188 μm.

6. The sealing sheet according to claim 5, characterized in that: The protective film is directly laminated with the resin composition layer, The ratio of the root mean square height Sq specified in ISO 25178 on the surface of the protective film in contact with the resin composition layer to the thickness Ta of the resin composition layer is 0.01% to 30%.

7. The sealing sheet according to any one of claims 1 to 6, characterized in that: The peak top intensity (tan δ peak intensity) of the loss tangent of the resin composition layer obtained by dynamic viscoelasticity measurement in the range of -50°C to 80°C is 0.6 to 2.

2.

8. The sealing sheet according to claim 7, characterized in that: The optical semiconductor element is a micro light emitting diode.

9. A display having a sealing layer, characterized in that: The sealing layer contains 5.3 to 48.2 parts by mass of metal oxide particles (B) having a number average primary particle diameter of 5 to 50 nm based on 100 parts by mass of the total of the resin (A), the monomer and the oligomer, and has a refractive index of 1.45 to 1.65.

Citation Information

Patent Citations

  • Information processing device, information processing method, and information processing program

    JP2023135317A

  • Melt blown non-woven fabric and filter having the same

    JP2023173435A

  • Optical semiconductor device sealing sheet

    WO2021200035A1

Cited By

  • Sealing sheet, display, and method for manufacturing the same

    CN119081572A

  • Sealing sheet and method for manufacturing display

    CN119081572B